Modified intermediate layer containing sulfonic acid, three-dimensional polymer framework and cross-linked polymer for lithium battery
By introducing a modified intermediate layer between the lithium metal anode and the solid electrolyte, the problem of lithium dendrites is solved, the current density and cyclic stability of the solid lithium metal battery are improved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202310859240.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
AI Technical Summary
Lithium metal anode is prone to form lithium dendrites in solid lithium metal batteries, resulting in reduced performance, including reduced critical current density and increased interface resistance.
Using a modified intermediate layer, including a three-dimensional polymer frame and a crosslinked polymer, prepared by electrospinning technology, contains sulfonic acid-containing compounds and lithium salts, as lithium ion conductive paths, inhibit the formation of lithium dendrites and maintain the electrodes. Intimate contact with solid electrolyte.
It significantly improves the critical current density and cycling stability of solid-state lithium metal batteries, extends the battery life, and reduces the interface resistance.
Smart Images

Figure CN119315092A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium ion battery, and more particularly, to a modified intermediate layer between an electrode and a solid electrolyte of a lithium ion battery. Background Art
[0002] Fossil fuels have long been the main source of energy. However, fossil fuels are limited, and when they are burned to generate heat, they produce greenhouse gases and cause air pollution. In order to reduce dependence on fossil fuels, people develop and use renewable energy sources such as solar and wind energy to generate electricity. The generation of electrical energy has stimulated the demand for rechargeable batteries. Rechargeable batteries can store the electrical energy generated by renewable energy (and fossil fuels) in the form of chemical energy. When connected to an external circuit, a chemical reaction occurs inside the rechargeable battery, converting chemical energy into electrical energy. This conversion is reversible, and charging can realize the chemical energy stored in the rechargeable battery again, completing the reversal of the chemical reaction.
[0003] A variety of rechargeable batteries have been developed, each using different materials to promote different chemical reactions to convert stored chemical energy into electrical energy. Examples include nickel-cadmium (Ni-Cd), nickel-metal hydride (NiMH), lead-acid, and lithium-ion (Li-ion). Compared to other rechargeable batteries, lithium-ion rechargeable batteries (hereafter referred to as lithium-ion batteries) have the characteristics of high energy density, high cycle life, and no "memory effect".
[0004] Lithium-ion batteries usually include an anode (negative electrode), a cathode (positive electrode), and an electrolyte. The electrolyte of the first generation of lithium-ion batteries is a liquid electrolyte solution. Currently, liquid electrolyte solutions have been replaced by polymer electrolytes, which have been widely used in lithium-ion batteries. Solid-state electrolytes (SSE) for lithium-ion batteries are under development, which are superior to other liquid and polymer electrolytes in terms of life and energy density.
[0005] Research on lithium-ion batteries focuses on optimizing the composition of the anode and cathode for use in combination with solid electrolytes for lithium-ion batteries. For example, some lithium-ion batteries based on solid electrolytes use cathodes and anodes made of lithium cobalt oxide and lithium titanate, respectively, among others. Other lithium-ion batteries based on solid electrolytes under development use anodes containing lithium metal. Solid-state lithium-ion batteries using lithium metal as an anode are also called solid-state lithium metal batteries (SSLMB).
[0006] Several solid electrolytes have been investigated for solid-state lithium metal batteries, such as lithium oxyphosphide and nitrogen (LiPON) or lithium garnet (Li7La3Zr2O 12 , LLZO). In a solid-state lithium metal battery, the lithium metal anode and the solid electrolyte are in direct contact. However, the lithium metal anode tends to produce lithium dendrites at the anode. Lithium dendrites are branches of lithium metal that grow from the surface of the lithium metal anode and penetrate into the solid electrolyte. Lithium dendrites cause various problems, such as reducing the performance of solid-state lithium metal batteries, including reducing the critical current density (CCD) of solid-state lithium metal batteries. Summary of the invention
[0007] The present disclosure provides a modified interlayer for the interface of a lithium-containing anode and a solid electrolyte. The modified interlayer includes a three-dimensional polymer framework electrospun together with a sulfonic acid. The three-dimensional polymer framework has interconnected pores, which are occupied by a cross-linked polymer, a cross-linked solvent, and a lithium salt. The modified interlayer exhibits excellent ionic conductivity, in part due to the presence of sulfonic acid-containing compounds and their reaction products that are conducive to lithium ion transport. A solid-state lithium metal battery using the modified interlayer suppresses the formation of lithium dendrites and exhibits a superior critical current density.
[0008] The modified intermediate layer serves as a continuous transport path for lithium ions between the solid electrolyte and the electrode (such as the anode), ensuring high lithium ion conductivity at the interface. The viscoelasticity of the modified intermediate layer enables it to maintain close contact between the solid electrolyte and the modified intermediate layer and between the modified intermediate layer and the electrode (such as the anode), and even in the case of severe lithium morphological changes (such as expansion and contraction of the electrode), it can maintain good interfacial contact. In various aspects, during the cycle of the solid-state lithium-containing battery, a portion of the modified intermediate layer can also enter and / or exit from the pores of the solid electrolyte. In addition, the viscoelasticity of the modified intermediate layer allows the inclusion of a second electrode (e.g., a cathode) with a relatively high load and higher capacity lithium deposition and stripping at the electrode, as shown in the embodiments of this article.
[0009] Without the modified interlayer, the contact area between the solid electrolyte and the electrode (as a solid-solid interface) will be more limited, leading to the formation of lithium dendrites at the interface and reducing the critical current density. During the cycling of solid-state lithium-containing batteries, the limited contact area will be further exacerbated by the pulverization of lithium metal at the electrode and the formation of pores. The addition of the modified interlayer effectively prevents these problems.
[0010] In some aspects, the modified intermediate layer can be formed by heat curing the modified reaction mixture and the electrospinning polymer, wherein the modified reaction mixture and the electrospinning polymer are located between the anode and the solid electrolyte. The heat curing reaction mixture enables the reaction mixture and the resulting modified intermediate layer to be in close contact with the surface of the solid electrolyte. When the solid electrolyte is porous (e.g., etched), this may be particularly beneficial because the modified reaction mixture can enter and / or the modified intermediate layer can be fixed in the pores of the solid electrolyte, which can increase the critical current density that the resulting battery can withstand and / or reduce the interfacial resistance of the resulting battery, as shown in the embodiments of this article. Alternatively, in some aspects, the modified intermediate layer can be cured before being placed between the anode and the solid electrolyte, which can simplify the final assembly of the resulting solid-state lithium-containing battery.
[0011] Some exemplary aspects of the present disclosure are described below, but it should be understood that any features of each aspect may be used alone or in combination with each other.
[0012] In a first aspect of the present disclosure, a solid-state lithium-containing battery comprises: electrode; solid electrolyte; and A modified intermediate layer, the modified intermediate layer is located between the electrode and the solid electrolyte and is in direct contact therewith, the modified intermediate layer comprising: A three-dimensional polymer framework includes (i) electrospun polymer nanofibers having a diameter in the range of 10 nm to 50 nm, (ii) a framework additive contained in the electrospun polymer nanofibers, the framework additive including a sulfonic acid-containing compound, and (iii) pores between the electrospun polymer nanofibers. cross-linked polymers in the pores of the three-dimensional polymer framework; Cross-linking solvents in the pores of the three-dimensional polymer framework; and Lithium salts in the pores of three-dimensional polymer frameworks.
[0013] The second aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first aspect, wherein the electrospun polymer nanofibers include one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyvinylidene fluoride, polyurethane, polyacrylonitrile, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyacrylic acid, carboxymethyl cellulose, polyethylene oxide, poly(acrylonitrile-co-butadiene-co-styrene) and polyimide.
[0014] A third aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the second aspect, wherein the electrospun polymer nanofibers include poly(vinylidene fluoride-co-hexafluoropropylene).
[0015] The fourth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to third aspects, wherein the sulfonic acid compound includes one or more of D(+)-10-camphorsulfonic acid (DCA), DL-10-camphorsulfonic acid, L(-)-camphorsulfonic acid, benzenesulfonic acid, o-cresol-4-sulfonic acid and 2-naphthalenesulfonic acid.
[0016] The fifth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the fourth aspect, wherein the sulfonic acid compound includes D(+)-10-camphorsulfonic acid.
[0017] A sixth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to fifth aspects, wherein the three-dimensional polymer framework substantially does not contain nodules of electrospun polymer nanofibers.
[0018] The seventh aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to sixth aspects, wherein the cross-linked polymer includes a cross-linked polymer network, which includes units of one or more of ether-containing acrylates, ether-containing methacrylates, alkyl carbonates, or a combination thereof.
[0019] An eighth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to seventh aspects, wherein the cross-linked polymer network of the cross-linked polymer includes a fluoroether additive.
[0020] The ninth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the eighth aspect, wherein the fluoroether additive includes one or more of polyperfluoromethyl isopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), and fluorobenzene (FB).
[0021] The tenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to ninth aspects, wherein the cross-linking solvent includes one or more of fluoroethylene carbonate (FEC), vinyl carbonate (VC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene sulfinate (FES), difluoroethylene carbonate (DFEC) and trifluoroethyl methyl carbonate (FEMC).
[0022] The eleventh aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to tenth aspects, wherein the lithium salt includes lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)
[0023] The twelfth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to eleventh aspects, wherein the modified intermediate layer has a compressed thickness when it is compressed between the electrode and the solid electrolyte, and the modified intermediate layer has an uncompressed thickness when it is not compressed between the electrode and the solid electrolyte, and the ratio of the uncompressed thickness to the compressed thickness is 2 to 10.
[0024] The thirteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twelfth aspects, wherein the compressed thickness of the modified intermediate layer between the electrode and the solid electrolyte when compressed is in the range of 2 μm to 20 μm.
[0025] The fourteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to thirteenth aspects, wherein the ionic conductivity of the modified intermediate layer at 25° C. is within 4.5×10 -4 S / cm to 7.5×10 -4 S / cm range.
[0026] A fifteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to fourteenth aspects, wherein the electrode includes a lithium-containing anode, and the modified intermediate layer is located between the lithium-containing anode and the solid electrolyte.
[0027] A sixteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to fifteenth aspects, wherein the electrode includes lithium metal.
[0028] A seventeenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the sixteenth aspect, further comprising: a second electrode including a lithium metal electrode, wherein the solid electrolyte is located between the electrode and the second electrode, Wherein, the solid-state lithium-containing battery is a solid-state lithium metal symmetrical battery.
[0029] An eighteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to seventeenth aspects, wherein the solid electrolyte includes lithium garnet ceramics.
[0030] A nineteenth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the eighteenth aspect, wherein the main phase of the lithium garnet ceramic includes at least one of the following: (i)Li 7-3a LqCy a O 12 , characterized in that Q = Al, Ga or Fe, and 0<a<0.33; (ii)Li7La 3-b ZlUT b O 12 , characterized in that M = Bi or Y, and 0<b<1; (iii)Li 7-c LqCy 2-c N c O 12 , characterized in that N=In, Si, Ge, Sn, V, W, Te, Nb or Ta, and 0<c<1, or a combination thereof.
[0031] The twentieth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the eighteenth aspect, wherein the main phase of the lithium garnet ceramic includes Li7La3Zr2O 12 .
[0032] The twenty-first aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the eighteenth aspect, wherein the lithium garnet ceramic has a main phase of a lithium garnet ceramic doped with one or more dopants.
[0033] The twenty-second aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the eighteenth aspect, wherein the solid electrolyte is a composite material composed of two or more ceramic materials.
[0034] A twenty-third aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to sixteenth aspects, further comprising: A cathode comprising one or more of the following: lithium cobalt oxide (LiCoO2); lithium nickel oxide (LiNiO2); 1+x Mn 2-x Lithium manganate represented by O4, wherein x is 0 to 0.33; LiNi 1-y M y Ni-type lithium nickel oxide represented by O2, wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3; LiNi z Co m Mn 1-z-m A lithium nickel cobalt manganese material represented by O2, wherein x is 0 to 1, y is 0 to 1, and z+m<1; and combinations thereof; and The electrolyte, located between the cathode and the solid electrolyte, wherein the electrode is a cathode, Wherein, the solid-state lithium-containing battery is a solid-state lithium-containing full battery.
[0035] The twenty-fourth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twenty-third aspects, wherein the solid-state lithium-containing battery has a current density of 3.5 mA / cm at 25° C. 2 or higher critical current density.
[0036] The twenty-fifth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the twenty-fourth aspect, wherein the solid-state lithium-containing battery has a current density of 4.5 mA / cm at 25° C. 2 or higher critical current density.
[0037] The twenty-sixth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twenty-fifth aspects, wherein the coulombic efficiency of the solid-state lithium-containing battery is greater than or equal to 90% in at least 50 charge and discharge cycles at 25° C. and 0.5C.
[0038] The twenty-seventh aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twenty-fifth aspects, wherein the coulombic efficiency of the solid-state lithium-containing battery is greater than or equal to 90% in at least 200 charge and discharge cycles at 25° C. and 0.5C.
[0039] The twenty-eighth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twenty-seventh aspects, wherein the capacity retention rate of the solid-state lithium-containing battery after 50 cycles of charge and discharge at 0.5C and 25°C is about 80% or higher.
[0040] The twenty-ninth aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of the first to twenty-eighth aspects, wherein the capacity retention rate of the solid-state lithium-containing battery is about 90% or higher after 100 cycles of charge and discharge at 0.5C and 25°C.
[0041] The thirty-first aspect of the present disclosure may include any one of the first to twenty-ninth aspects of the solid-state lithium-containing battery, wherein the solid-state lithium-containing battery has an interface resistance of about 400 Ωcm at 25° C. 2 or smaller.
[0042] The thirty-first aspect of the present disclosure may include any one of the thirty aspects of the solid-state lithium-containing battery, wherein the interface resistance of the solid-state lithium-containing battery at 25° C. is about 250 Ωcm 2 or smaller.
[0043] The thirty-second aspect of the present disclosure may include any one of the solid-state lithium-containing batteries of aspects one to thirty-first, wherein the solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte.
[0044] In a thirty-third aspect of the present disclosure, a method for manufacturing a solid-state lithium-containing battery comprises: electrospinning a solution comprising a polymer and a framework additive to obtain a three-dimensional (3D) polymer framework, wherein the three-dimensional polymer framework comprises (i) electrospun polymer nanofibers and (ii) pores between electrospun polymer nanofibers, wherein the electrospun polymer nanofibers comprise the polymer and the framework additive integrated into the electrospun polymer nanofibers; and contacting the three-dimensional polymer framework with a monomer reaction mixture comprising (i) a cross-linkable monomer or prepolymer, (ii) a cross-linking solvent, and (iii) a lithium salt; The crosslinkable monomer or prepolymer in the monomer reaction mixture is reacted to form a modified interlayer, wherein the modified interlayer comprises (i) the three-dimensional polymer framework, (ii) a crosslinked polymer within the pores of the three-dimensional polymer framework, (iii) a crosslinking solvent within the pores of the three-dimensional polymer framework, and (iv) a lithium salt within the pores of the three-dimensional polymer framework, wherein the framework additive comprises a sulfonic acid-containing compound.
[0045] The thirty-fourth aspect of the present disclosure may include any one of the methods of the thirty-third aspect, wherein the polymer includes one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyvinylidene fluoride, polyurethane, polyacrylonitrile, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyacrylic acid, carboxymethyl cellulose, polyethylene oxide, poly(acrylonitrile-co-butadiene-co-styrene) and polyimide.
[0046] A thirty-fifth aspect of the present disclosure may include any one method of the thirty-third to thirty-fourth aspects, wherein the weight percentage of the framework additive is in the range of 0.10 wt % to 3.0 wt %.
[0047] The thirty-sixth aspect of the present disclosure may include any one of the methods of aspects thirty-third to thirty-fifth, wherein the sulfonic acid compound includes one or more of D(+)-10-camphorsulfonic acid, DL-10-camphorsulfonic acid, L(-)-camphorsulfonic acid, benzenesulfonic acid, o-cresol-4-sulfonic acid and 2-naphthalenesulfonic acid.
[0048] The thirty-seventh aspect of the present disclosure may include any one method of the thirty-sixth aspect, wherein the sulfonic acid-containing compound comprises D(+)-10-camphorsulfonic acid.
[0049] A thirty-eighth aspect of the present disclosure may include any one method of aspects thirty-six to thirty-seven, wherein the three-dimensional polymer framework exhibits an absorption capacity of greater than or equal to 800% of the monomer reaction mixture.
[0050] The thirty-ninth aspect of the present disclosure may include any one method of aspects thirty-third to thirty-eighth, wherein the cross-linkable monomer or prepolymer comprises one or more alcohol-containing acrylates, alcohol-containing methacrylates, vinyl carbonate or a combination thereof.
[0051] The fortieth aspect of the present disclosure may include any one of the methods of the thirty-third to thirty-eighth aspects, wherein the crosslinkable monomer or prepolymer includes diethylene glycol diacrylate (DEGDA), diethylene glycol dimethacrylate (DEGDMA), triethylene glycol diacrylate (TEGDA), triethylene glycol dimethacrylate (TEGDMA), tetraethylene glycol diacrylate (TTEGDA), glycidyl methacrylate, polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polypropylene glycol diacrylate (PPGDA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), diethylene glycol diacrylate (DDA), diethylene glycol dimethacrylate (DDMA), ethoxylated trimethylolpropane triacrylate (ETPTA), acrylate functionalized ethylene oxide One or more of alkyl, butanediol dimethacrylate, ethoxylated neopentyl glycol diacrylate (NPEOGDA), propoxylated neopentyl glycol diacrylate (NPPOGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane triacrylate (TMPTMA), pentaerythritol triacrylate (PETA), ethoxylated propoxylated trimethylolpropane triacrylate (TMPEOTA) / (TMPPOTA), propoxylated glycerol triacrylate, tris(2-hydroxyethyl)isocyanurate (THEICTA), pentaerythritol tetraacrylate (PETTA), pentaerythritol pentaacrylate (DPEPA), dimethylenepropane tetraacrylate (DTMPTTA), diglycidyl esters, diallyl esters, acrylamide, divinylbenzene, poly(ethylene glycol methyl ether methacrylate) (PEGMEMA).
[0052] The forty-first aspect of the present disclosure may include any one method of aspects thirty-third to thirty-eighth, wherein the cross-linkable monomer or prepolymer includes vinyl ethylene carbonate.
[0053] The forty-second aspect of the present disclosure may include any one of the methods of aspects thirty-third to forty-first, wherein the cross-linking solvent includes one or more of fluoroethylene carbonate (FEC), vinyl carbonate (VC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and fluoroethylene sulfinate (FES).
[0054] The forty-third aspect of the present disclosure may include any one method of the thirty-third to forty-second aspects, wherein the lithium salt includes lithium bistrifluoromethanesulfonyl imide (LiTFSI).
[0055] A forty-fourth aspect of the present disclosure may include any one method of aspects thirty-third to forty-third, wherein the monomer reaction mixture further comprises a fluoroether additive.
[0056] The forty-fifth aspect of the present disclosure may include any one of the methods of aspects thirty-third to forty-third, wherein the fluoroether additive includes one or more of polyperfluoromethyl isopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), and fluorobenzene (FB).
[0057] The forty-sixth aspect of the present disclosure may include any one method of aspects thirty-third to forty-fifth, wherein the monomer reaction mixture further comprises a photoinitiator, and the reaction comprises irradiating the crosslinkable monomer or prepolymer in the monomer reaction mixture with ultraviolet light.
[0058] A forty-seventh aspect of the present disclosure may include any one method of the thirty-third to forty-fifth aspects, further comprising: The modified intermediate layer is disposed between the lithium-containing electrode and the solid electrolyte.
[0059] The forty-eighth aspect of the present disclosure may include any one method of the thirty-third to forty-fifth aspects, wherein the monomer reaction mixture further comprises a thermal initiator, and the reacting comprises heating the monomer reaction mixture.
[0060] The forty-ninth aspect of the present disclosure may include any one method of the forty-eighth aspect, wherein the method further comprises positioning the three-dimensional polymer framework and the monomer reaction mixture between a lithium-containing electrode and a solid electrolyte after the contacting and before the reacting.
[0061] The fiftieth aspect of the present disclosure may include any one method of the forty-ninth aspect, wherein the solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte.
[0062] The fifty-first aspect of the present disclosure may include any one of the methods of the forty-seventh, forty-nineth or fiftieth aspects, wherein the solid electrolyte comprises a lithium garnet ceramic.
[0063] Aspect 52 of the present disclosure may include any one method of aspects 33 to 51, wherein the modified intermediate layer has a compressed thickness when compressed between the electrode and the solid electrolyte, has an uncompressed thickness when not compressed between the electrode and the solid electrolyte, and the ratio of the uncompressed thickness to the compressed thickness is 2 to 10.
[0064] A fifty-third aspect of the present disclosure may include any one of the methods of aspects thirty-third to fifty-second, wherein the solid-state lithium-containing battery has a current density of 3.5 mA / cm at 25° C. 2 or higher critical current density.
[0065] The fifty-fourth aspect of the present disclosure may include any one method of aspects thirty-third to fifty-third, wherein the capacity retention rate of the solid-state lithium-containing battery is about 80% or higher after 50 cycles of charging and discharging at 0.5C and 25°C.
[0066] The fifty-fifth aspect of the present disclosure may include any one method of aspects thirty-third to fifty-third, wherein the capacity retention rate of the solid-state lithium-containing battery after 100 cycles of charging and discharging at 0.5C and 25°C is about 90% or higher.
[0067] A fifty-sixth aspect of the present disclosure may include any one of the methods of aspects thirty-third to fifty-fifth, wherein the interface resistance of the solid-state lithium-containing battery at 25° C. is about 400 Ωcm 2 or smaller.
[0068] A fifty-seventh aspect of the present disclosure may include any one of the methods of the fifty-sixth aspect, wherein the interface resistance of the solid-state lithium-containing battery at 25° C. is about 250 Ωcm 2 or smaller.
[0069] A fifty-eighth aspect of the present disclosure may include any one method of aspects thirty-third to fifty-seven, wherein the solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] The above and other features and advantages of various aspects of the present disclosure will be better understood when the following detailed description is read with reference to the accompanying drawings, in which:
[0071] Figure 1 is a schematic diagram of a cross-sectional view of a solid-state lithium-containing battery showing a modified interlayer of the present disclosure positioned between an electrode and a solid electrolyte.
[0072] Figure 2 yes Figure 1Schematic diagram of a cross-sectional view of a modified intermediate layer in which (i) is a three-dimensional polymer framework made of electrospun polymer nanofibers, in which a sulfonic acid framework additive is dispersed in the polymer network of the nanofibers, and (ii) is a cross-linked polymer in which a cross-linking solvent and a lithium salt are dispersed in the framework of the cross-linked polymer.
[0073] Figure 3 Is prepared Figure 1 A flow chart of a method for modifying an intermediate layer in a three-dimensional polymer framework is provided, wherein an electrospinning step for preparing a three-dimensional polymer framework, a contacting step for allowing a monomer reaction mixture to contact and enter the pores of the three-dimensional polymer framework, and a cross-linking step for cross-linking the monomer reaction mixture into a cross-linked polymer are shown.
[0074] Figure 4 is a schematic diagram of the electrospinning apparatus used to perform Figure 3 Electrospinning steps.
[0075] Figure 5 is a schematic diagram of the contact process between the three-dimensional polymer framework and the monomer reaction mixture. Figure 3 The contact step in .
[0076] Figure 6 Schematic diagram of UV-induced crosslinking of components of a monomer reaction mixture, while the monomer reaction mixture is disposed within the pores of a three-dimensional polymer framework to produce Figure 1 Modified middle layer.
[0077] Figure 7 is a scanning electron microscope (SEM) image of a three-dimensional polymer framework prepared by electrospinning a solution containing 1.0 wt % sulfonic acid in Example 1, showing the electrospun polymer nanofibers and the pores between the nanofibers.
[0078] Figure 8 is a cross-sectional SEM image of the three-dimensional polymer framework of Example 1, showing that the thickness of the three-dimensional polymer framework is 38 μm.
[0079] Fig. 9 is a surface SEM image of the modified interlayer of Example 1, showing the modified interlayer formed by cross-linking of the components of the monomer reaction mixture in the pores of the three-dimensional polymer framework after the cross-linking step.
[0080] Fig.10 is a cross-sectional SEM image of the modified interlayer of Example 1, showing that the thickness of the modified interlayer is 40 μm, which is slightly thicker than the three-dimensional polymer framework produced after the electrospinning step.
[0081] Fig.111 is an optical image of Example 1, showing the modified interlayer after being subjected to a torsional force and the modified interlayer after the torsional force is released, indicating that the torsional force does not cause obvious permanent deformation.
[0082] Fig.12 The monomer reaction mixture is placed in the pores of a three-dimensional polymer framework to produce Figure 1 Schematic diagram of the modified intermediate layer and the simultaneous heating of the monomer reaction mixture.
[0083] Fig.13 is the Nyquist plot of Example 1, showing the impedance of the modified interlayer at different temperatures, especially the low real impedance at higher temperatures.
[0084] Fig.14 The graph of the voltage and current density over time during the critical current density test of the solid-state lithium-containing symmetrical battery assembled using the modified intermediate layer in Example 1 shows that the critical current density is about 4.0 mA / cm 2 .
[0085] Fig.15 It is a graph showing the voltage variation over time during the long-term constant current cycle test of the solid-state lithium-containing symmetrical battery in Example 1, which shows that the polarization curve is stable, and there is no lithium dendrite or polarization voltage drop.
[0086] Fig.16 Figure 2 is a SEM image and energy dispersive X-ray spectroscopy (EDS) analysis result of a lithium sheet, showing sulfur (S), oxygen (O), and fluorine (F) atoms formed on the surface of the lithium sheet due to the presence of sulfonic acid and its reaction products.
[0087] Fig.17 This is a rate performance test diagram of the solid-state lithium-containing full battery assembled using the modified intermediate layer in Example 1#, showing the changes in the discharge specific capacity and coulombic efficiency percentage with the number of cycles and C rate.
[0088] Fig.18 This is the same solid-state lithium-containing full battery rate performance test chart as Example 1#, showing the change of voltage with discharge specific capacity and C rate.
[0089] Fig.19 This is the cycle stability test diagram of the solid-state lithium-containing full battery in Example 1#, similar to Fig.17 The graph shows the results of 200 cycle tests.
[0090] Fig. 20 This is the cycle stability test diagram of the solid-state lithium-containing full battery in Example 1#, similar to Fig.18 The graph shows the change of voltage with discharge specific capacity and cycle number in 200 cycle test.
[0091] Fig.21 This is the solid-state lithium-containing full battery cycle stability test diagram of Example 1, which shows the discharge specific capacity and coulombic efficiency of another solid-state lithium-containing full battery, which includes a modified intermediate layer, but this time uses a higher nickel-cobalt-manganese (NCM) cathode loading, illustrating the capacity maintenance after 50 cycles.
[0092] Fig. 22 This is a graph of the cycle stability test of a solid-state lithium-containing full battery in Example 1*, which shows the change in voltage with discharge specific capacity and cycle number in a 50-cycle test.
[0093] Fig.23 is the Nyquist plot of Example 1* for a solid-state lithium-containing full cell with a higher NCM cathode loading, indicating that the interfacial resistance of the cell is about 304 Ωcm 2 .
[0094] Fig.24 is a Nyquist plot of Example 2 for a modified interlayer prepared by electrospinning from a solution containing 0.5 wt % sulfonic acid, showing the ionic conductivity results of the modified interlayer.
[0095] Fig.25 It is a critical current density test diagram of Example 2, which shows the change of voltage and current density over time of a solid-state lithium-containing symmetrical battery manufactured using a modified intermediate layer.
[0096] Fig.26 Graphs of the ionic conductivity of the modified intermediate layer made of the three-dimensional polymer frameworks of Examples 1-4, wherein the three-dimensional polymer frameworks were prepared from sulfonic acid solutions of different weight percentages using an electrospinning method, indicating that 0.5 wt % sulfonic acid has the highest ionic conductivity.
[0097] Fig. 27 is a scanning electron microscope image of the three-dimensional polymer framework of Comparative Example 1, in which no sulfonic acid was used in the preparation of the modified interlayer, showing nanofibers with much larger diameters and more polymer nodules than the modified interlayer described herein.
[0098] Fig.28 Comparative Example 2 shows the variation of voltage with discharge specific capacity and cycle number in the cycle performance test when the modified intermediate layer is not included in the solid-state lithium-containing full battery, indicating that the battery fails during the second cycle.
[0099] Fig.29 : is a cross-sectional SEM image of the solid electrolyte having a porous layer of Examples 5 and 7, showing that the thickness of the porous layer is about 13 μm.
[0100] Fig.30This is a curve diagram of the discharge specific capacity and coulombic efficiency of a solid-state lithium-containing full battery assembled using a modified intermediate layer in Example 7*, illustrating the maintenance of capacity after 100 cycles.
[0101] Fig.31 Example 7* Fig.30 Variation of the mid-range voltage with specific capacity and cycle number for selected cycles.
[0102] Fig.32 This is a curve diagram of the discharge specific capacity and coulombic efficiency of another solid-state lithium-containing full battery assembled using a modified intermediate layer in Example 6*, showing the capacity maintenance of 67 cycles before short circuit.
[0103] Fig.33 Example 6* Fig.32 Variation of the mid-range voltage with specific capacity and cycle number for selected cycles. DETAILED DESCRIPTION
[0104] refer to Figure 1-2 , the solid-state lithium-containing battery 10 includes an electrode 12, a solid electrolyte 14, and a modified intermediate layer 16 located between the electrode 12 and the solid electrolyte 14. The modified intermediate layer 16 is in direct contact with the electrode 12 and the solid electrolyte 14. Among other things, the modified intermediate layer 16 serves as a bridge for lithium ions to pass between the electrode 12 and the solid electrolyte 14.
[0105] The modified intermediate layer 16 includes a three-dimensional polymer framework 18. The three-dimensional polymer framework 18 includes polymer nanofibers 20 prepared by electrospinning, a framework additive 22, and pores 24 between the electrospun polymer nanofibers 20. The polymer nanofibers 20 prepared by electrospinning are formed by an electrospinning step that forms nanofibers having different properties from fibers formed by other methods. These characteristics of nanofibers prepared by electrospinning include nanometer-scale diameters, pores between nanofibers, and a collection of nanofibers in a mat-like form. The diameter 26 of the electrospun polymer nanofibers 20 of the present disclosure is in the range of 10nm to 50nm, although occasionally individual electrospun polymer nanofibers 20 may exceed this range.
[0106] like Figure 2As shown, the electrospun polymer nanofiber 20 includes a polymer 28. In various aspects, the electrospun polymer nanofiber 20 includes polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), polyurethane (PU), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyethylene glycol (PEG), polymethyl methacrylate (PMMA) polyacrylic acid, carboxymethyl cellulose (CMC), polyethylene oxide (PEO), poly(acrylonitrile-butadiene-styrene) (ABS) and polyimide (PI) and / or copolymers or derivatives thereof. In some aspects, the electrospun polymer nanofiber 20 includes poly(vinylidene fluoride-co-hexafluoropropylene) 28. The present disclosure provides examples of polymers 28 that can be used to prepare electrospun polymer nanofibers 20, which examples are not exclusive.
[0107] Throughout the disclosure, the "molecular weight" of a polymer chain is measured by high performance liquid chromatography (HPLC) calibrated with a polystyrene (PS) standard. As used herein, "molecular weight" refers to the number average molecular weight (Mn). The number average molecular weight of a polymer is calculated by adding the product of the molecular weight and the fraction of the polymer and the molecular weight. In some aspects, the molecular weight (Mn) of the polymer in the electrostatic spinning polymer nanofiber 20 can be about 50,000 Daltons (Da) or greater, about 100,000 Da or greater, about 150,000 Da or greater, about 200,000 Da or greater, about 25,000 Da or greater, about 300,000 Da or greater, about 350,000 Da or greater, about 500,000 Da or less, about 450,000 Da or less, or about 400,000 Da or less. In various aspects, the molecular weight (Mn) of the polymer in the electrospun polymer nanofibers 20 can be in the range of about 50,000 Da to about 100,000 Da, about 100,000 Da to about 800,000 Da, about 200,000 Da to about 600,000 Da, from about 300,000 Da to about 500,000 Da, or any range or sub-range therebetween.
[0108] like Figure 2 As shown, the framework additive 22 is integrated into the electrospun polymer nanofiber 20. As further explained below, during the electrospinning preparation process, the polymer 28 of the electrospun polymer nanofiber 20 and the framework additive 22 combine with each other and form a solid nanofiber structure, namely, the electrospun polymer nanofiber 20.
[0109] In some aspects, the framework additive 22 includes a sulfonic acid-containing compound. In an embodiment, the sulfonic acid-containing compound includes one or more of D (+) -10- camphorsulfonic acid (DCA), DL-10- camphorsulfonic acid, L (-) -camphorsulfonic acid, benzenesulfonic acid, o-cresol-4-sulfonic acid and 2-naphthalenesulfonic acid. In some aspects, the sulfonic acid-containing compound is or includes D (+) -10- camphorsulfonic acid (DCA). The presence of the sulfonic acid-containing compound improves the structural stability of the electrospun polymer nanofiber 20. For example, the sulfonic acid-containing compound is one of the reasons for the framework additive 22, and the three-dimensional polymer framework 18 is substantially free of nodules of the electrospun polymer nanofiber 20. Nodules are irregularly shaped or spherical electrospun nanofiber aggregates. Nodules are usually larger than the surrounding nanofibers and can be visually distinguished in a uniform and continuous nanofiber structure. Sulfonic acid-containing compounds provide other benefits, which will be discussed below.
[0110] like Figure 2As shown, the modified interlayer 16 also includes a cross-linked polymer 30, a cross-linking solvent 32 and a lithium salt 34 in the pores 24 of the three-dimensional polymer framework 18. In various aspects, the cross-linked polymer 30 includes a cross-linked polymer network, which includes units of one or more monomers and / or prepolymers. In further aspects, one or more monomers and / or prepolymers can be alcohol-containing acrylates, alcohol-containing methacrylates, ethylene carbonate or polymers, copolymers or derivatives thereof. For example, a polymer containing an alcohol-containing acrylate monomer has an ether-containing acrylate in the resulting polymer. Therefore, the polymer can contain one or more ether-containing acrylates, ether-containing methacrylates, ethylene carbonate or a combination thereof. The one or more monomers and / or prepolymers include diethylene glycol diacrylate (DEGDA), diethylene glycol dimethacrylate (DEGDMA), triethylene glycol diacrylate (TEGDA), triethylene glycol dimethacrylate (TEGDMA), tetraethylene glycol diacrylate (TTEGDA), glycidyl methacrylate, polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polypropylene glycol diacrylate (PPGDA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DDA), dipropylene glycol dimethacrylate (DDMA), ethoxylated trimethylolpropane triacrylate (ETPTA), acrylate functionalized ethylene oxide, butanediol One or more of alcohol dimethacrylate, ethoxylated neopentyl glycol diacrylate (NPEOGDA), propoxylated neopentyl glycol diacrylate (NPPOGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane triacrylate (TMPTMA), pentaerythritol triacrylate (PETA), ethoxylated propoxylated trimethylolpropane triacrylate (TMPEOTA) / (TMPPOTA), propoxylated glycerol triacrylate, tris(2-hydroxyethyl)isocyanurate (THEICTA), pentaerythritol tetraacrylate (PETTA), pentaerythritol pentaacrylate (DPEPA), dimethylenepropane tetraacrylate (DTMPTTA), diglycidyl ester, diallyl ester, acrylamide, divinylbenzene. In an embodiment, the crosslinked polymer 30 includes a crosslinked polymer network, including poly(ethylene glycol methyl ether methacrylate) (PEGMEMA). Examples of vinyl carbonates include vinyl ethylene carbonate (VEC) and polymers, copolymers and derivatives thereof. This list is not exclusive, and the crosslinked polymer network of the crosslinked polymer 30 may include other monomers and / or prepolymers.
[0111] In some aspects, the cross-linked polymer network of the cross-linked polymer 30 of the modified interlayer 16 includes an additive of a fluorinated organic compound, such as a fluoroether additive. In a further aspect, the fluoroether additive includes one or more of polyperfluoromethylisopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), and fluorobenzene (FB). These compounds are additives that increase the critical current density of the modified interlayer 16.
[0112] In some aspects, the cross-linking solvent 32 of the modified intermediate layer 16 includes one or more of fluoroethylene carbonate (FEC), vinyl carbonate (VC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene sulfinate (FES), difluoroethylene carbonate (DFEC) and trifluoroethyl methyl carbonate (FEMC). The cross-linking solvent can improve the electrochemical performance of the modified intermediate layer 16.
[0113] In some aspects, the lithium salt 34 of the modified intermediate layer 16 is incorporated into the cross-linked polymer 30 of the modified intermediate layer 16. The lithium salt 34 may include one or more of lithium bis(oxalato)borate (LiBOB), lithium difluorooxalate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiOTf), lithium tetrafluoroborate (LiBF4), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), bis(oxalate)borate tetrafluoroborate (LiBOB-LiBF4), and lithium difluorophosphate (LiDFP). In some aspects, the lithium salt 34 may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). By incorporating the lithium salt 34 into the cross-linked polymer 30, the modified intermediate layer 16 may achieve improved ionic conductivity.
[0114] In various aspects, the modified intermediate layer 16 has a compressed thickness 36 (eg Figure 1 ) and the uncompressed thickness 38 (as Figure 2As shown). The compressed thickness 36 refers to the situation where the modified intermediate layer 16 is sandwiched between the electrode 12 and the solid electrolyte 14 in the solid-state lithium-containing battery 10 and is compressed. In various aspects, the compressed thickness 36 of the modified intermediate layer 16 is in the range of 2μm to 20μm. For example, 3μm to 18μm, 4μm to 16μm, about 5μm to about 14μm, about 6μm to about 12μm, or any range or sub-range therebetween. The compressed thickness 36 can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, or in any range between these values (for example, from 6μm to 13μm, from 7μm to 14μm, etc.). The compressed thickness 36 may be less than 2 μm or greater than 20 μm.
[0115] The uncompressed thickness 38 refers to the thickness of the modified intermediate layer 16 when it is not compressed between two solid objects, such as between the electrode 12 and the solid electrolyte 14. In various aspects, the uncompressed thickness 38 of the modified intermediate layer 16 is in the range of 30 μm to 100 μm. For example, 35 μm to 90 μm, 35 μm to 80 μm, 40 μm to 70 μm, 40 μm to 60 μm, 40 μm to 50 μm, or any range or sub-range therebetween. The uncompressed thickness 38 can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm, or in any range between these values (e.g., from 35 μm to 45 μm, from 40 μm to 50 μm, etc.). The uncompressed thickness 38 may be less than 30 μm or greater than 100 μm.
[0116] In some aspects, the ratio of the uncompressed thickness to the compressed thickness can be 2 or more, 3 or more, 3.5 or more, 4 or more, 10 or less, 8 or less, 6 or less or 5 or less. In various aspects, the ratio of the uncompressed thickness to the compressed thickness can be 2 to 10, 3 to 8, 3.5 to 8, 4 to 6, or any range or sub-range therebetween. The ratio reflects the viscoelasticity of the polymer framework and / or the crosslinking in the modified interlayer. The viscoelasticity of the modified interlayer 16 enables it to maintain close contact between the solid electrolyte 14 and the modified interlayer 16 and between the modified interlayer 16 and the electrode 12 during severe lithium volume changes of the electrode 12 (e.g., expansion and contraction of the electrode 12).
[0117] The ionic conductivity of the modified interlayer 16 is a measure of the ability of the modified interlayer 16 to transport ions (e.g., lithium ions) between the electrode 12 and the solid electrolyte 14. In some aspects, the ionic conductivity of the modified interlayer 16 at 25° C. is within 4.5×10-4 S / cm to 7.5×10 -4 S / cm. The ionic conductivity of the modified intermediate layer 16 at 25°C may be 4.5×10 -4 S / cm, 5.0×10 -4 S / cm, 5.5×10 -4 S / cm, 6.0×10 -4 S / cm, 6.5×10 -4 S / cm, 7.0×10 -4 S / cm or 7.5×10 -4 S / cm, or any range between these values (e.g., from 5.0×10 -4 S / cm to 6.0×10 -4 S / cm, or from 5.5×10 -4 S / cm to 6.5×10 -4 S / cm, etc.). The ionic conductivity can be less than 4.5×10 -4 S / cm or greater than 7.5×10 -4 S / cm. Throughout the disclosure, the "ionic conductivity" of the modified interlayer is measured using electrochemical impedance spectroscopy (EIS) at the specified temperature based on the behavior at 1 megahertz (MHz). The "ionic conductivity" of the modified interlayer is measured using the modified interlayer positioned between a pair of stainless steel electrodes. Unless otherwise stated, the ionic conductivity is measured at 25°C.
[0118] As used herein, "interfacial resistance" is measured using electrochemical impedance spectroscopy (EIS) at a frequency of 0.1 Hz to 1 megahertz (MHz) at 25°C. Unless otherwise specified, EIS was measured at 25°C using a PGSTAT320N (Metrohm Autolab) impedance analyzer. The Nyquist plot consists of the real component of the impedance on the horizontal axis (Z' in Ωcm 2 The imaginary component of impedance on the vertical axis (Z' in Ωcm 2 (represented) composition. Throughout the disclosure, "interface resistance" is defined as the difference between the real components of the impedance at the endpoints of the arc in the EIS result (i.e., the Nyquist plot), where the higher endpoint is considered to be the inflection point in the impedance result. To determine the "interface resistance", the battery is configured for use with a lithium-containing anode disposed on a modified intermediate layer and a cathode disposed on a second major surface of the solid electrolyte opposite to the first major surface, the modified intermediate layer being disposed on the first major surface of the solid electrolyte. In various aspects, the interface resistance of the solid-state lithium-containing battery 10 and / or the modified intermediate layer 16 can be approximately 400Ωcm 2 Or smaller, about 350Ωcm 2 Or smaller, about 320Ωcm 2 or less, or about 310Ωcm2 or smaller.
[0119] In various aspects, electrode 12 includes lithium (eg, lithium metal or a lithium-containing alloy). In some aspects, electrode 12 includes lithium metal. In various aspects, electrode 12 is an anode of solid-state lithium-containing battery 10.
[0120] The solid electrolyte 14 may include lithium garnet and / or a composite material formed by combining two or more ceramics. In some aspects, the solid electrolyte 14 is a composite material combining two or more ceramics. For example, the solid electrolyte 14 may be a lithium garnet ceramic doped with tantalum (Ta) and tungsten (W) (e.g., LLZT-2LWO). Examples of other combinations of the solid electrolyte 14 include lithium lanthanum zirconium oxide and lithium phosphate (e.g., LLZO-Li3PO4), lithium aluminum germanium phosphate and polyvinylidene fluoride (e.g., LAGP-PVDF), polyethylene glycol and lithium bis(oxalatoborate) (e.g., PEO-LiBOB), and lithium lanthanum titanate and lithium bis(trifluoromethanesulfonyl)imide (e.g., LLTO-LiTFSI).
[0121] In various aspects, the solid electrolyte 14 includes a lithium garnet ceramic that is stable with lithium (e.g., lithium ions, lithium metal) and has high ionic conductivity to provide efficient lithium ion transport capabilities. The lithium garnet ceramic may have Li7La3Zr2O 12 The main phase may be doped with one or more doping elements. For example, a lithium garnet ceramic may have Li 7-3a LqCy a O 12 The main phase is Li7La, where Q = Al, Ga or Fe, 0 < a < 0.33; (ii) Li7La 3-b ZlUT b O 12 , where M = Bi or Y, 0 < b < 1. In addition, lithium garnet ceramics may have Li 7-c LqCy 2-c N c O 12 The main phase is wherein N=In, Si, Ge, Sn, V, W, Te, Nb or Ta, and 0<c<1.
[0122] In some aspects, the solid electrolyte 14 is a lithium garnet ceramic composed of a lithium garnet major phase and an additive minor phase. The additive minor phase can be an oxide additive, such as lithium zirconium oxide (Li n ZrO (n+4) / 2 , where 2≤n≤10), lithium titanium oxide (Li d TiO (d+4) / 2 , where 0.66≤d≤4), lithium tungstate (Li w WO(e+6) / 2 , where 1 / 3≤e≤6), lithium silicate (Li f SiO (f+4) / 2 , where 1 / 2≤f≤8), lithium gallium oxide (Li g GaO (g+3) / 2 , where 1≤g≤5), lithium aluminate (Li h AlO (h+3) / 2 , where 1≤h≤5), lithium molybdate (Li k MoO (k+6) / 2 , where 1≤k≤4), lithium tantalum oxide (Li p TaO (p+5) / 2 , where 1≤p≤7), lithium niobium oxide (LiNbO3), tin oxide (Li q SnO (q+4) / 2 , where 2≤q≤8), indium oxide (Li u InO (u+3) / 2 , where 1≤u≤3), arsenic oxide (Li w AsO (w+5) / 2 , where 1≤w≤3), antimony oxide (Li v SbO (v+5) / 2 , wherein 1≤v≤7), MgO, CaO, Y2O3, La2O3, ZrO2, Al2O3, Ga2O3, Ta2O5, Nb2O5, B2O3, ZnO and Er2O3. In various aspects, the solid electrolyte 14 also includes lithium tungstate.
[0123] The solid electrolyte 14 may include pores facing the first electrolyte 12. In various aspects, a portion of the modified intermediate layer 16 may be located within one or more pores in the solid electrolyte. In further aspects, during the cycle of the solid-state lithium-containing battery 10, the portion of the modified intermediate layer 16 may enter the pores of the solid electrolyte 14 and retract therefrom. Alternatively, in further aspects, a portion of the modified intermediate layer 16 may be within the pores of the solid electrolyte 14 throughout the cycle of the solid-state lithium-containing battery 10 to ensure continuous, intimate contact and ion transport therebetween.
[0124] The solid-state lithium-containing battery 10 is also equipped with a second electrode 40, wherein in various aspects, the solid-state lithium-containing battery 10 can be a solid-state lithium-containing symmetric battery 10 having a lithium metal first electrode 12 and a lithium metal second electrode 40. Unlike other types of lithium-ion batteries that typically use different materials for positive and negative electrodes, the solid-state lithium metal symmetric battery 10 uses the same material as the electrode 12 and the electrode 40. One advantage of this design is that the solid-state lithium-containing battery 10 can be charged and discharged faster because there is no need to balance the charge between two different electrodes.
[0125] Alternatively, in other aspects, the solid-state lithium-containing battery 10 includes a cathode as the second electrode 40, making it a solid-state lithium-containing full battery 10. The cathode can be made of various materials, such as lithium cobalt oxide (LiCoO2); lithium nickel oxide (LiNiO2); 1+x Mn 2-x Lithium manganate represented by O4, wherein x is 0 to 0.33; LiNi 1-y M y Ni-type lithium nickel oxide represented by O2, wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3; LiNi z Co m Mn 1-z-m O2 represents a lithium nickel cobalt manganese material, where z is 0 to 1, m is 0 to 1, and z + m < 1. For example, when z is 0.6 and m is 0.2, the cathode may include LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM). The cathode can also be made of other materials.
[0126] In some aspects, an electrolyte is placed between the cathode (as the second electrode 40) and the solid electrolyte 14. In further aspects, the electrolyte may include a lithium salt, which may include one or more compounds discussed above with reference to the lithium salt 34. In even further aspects, the electrolyte may further include a sulfone compound. Exemplary aspects of sulfone compounds include sulfolane, 3-methylsulfolane, dimethyl sulfone, ethyl methyl sulfone, or a combination thereof. In various aspects, the molar ratio of the lithium salt to the sulfone compound may be about 0.125 (1:8) or greater, about 0.143 (1:7) or greater, about 0.167 (1:6) or greater, about 0.20 (1:5) or greater, about 0.25 (1:4) or greater, about 1 (1:1) or less, about 0.5 or less (1:2), about 0.4 or less, or about 0.333 (1:3) or less. In various aspects, the molar ratio of the lithium salt to the sulfone compound can be from about 0.125 to about 1, from about 0.143 to about 1, from about 0.167 to about 1, from about 0.20 to about 1, from about 0.25 to about 0.5, from about 0.25 to 0.4, and from about 0.25 to 0.333, or any range or sub-range therebetween. In further aspects, the ratio of the volume of the electrolyte to the surface area of the cathode can be about 5 μL / cm 2 or larger, about 10 μL / cm 2 Above, about 15μL / cm 2 Below, about 20μL / cm 2 Below, about 18μL / cm 2 Or smaller, or about 15μL / cm 2In a further aspect, the ratio of the volume of the electrolyte to the surface area of the cathode can be from about 5 μL / cm 2 About 20 μL / cm 2 , from about 10μL / cm 2 To about 18μL / cm 2 , from about 12μL / cm 2 About 18μL / cm 2 , from about 15μL / cm 2 To about 18μL / cm 2 or any range or sub-range therebetween.
[0127] In some aspects, such as Figure 1 As shown, the solid-state lithium-containing battery 10 may further include one or more current collectors 42, 44. In a further aspect, the electrode 12, the solid electrolyte 14, and the second electrode 40 may be located between a pair of current collectors 42, 44. The current collectors may be made of a conductive material such as copper or aluminum and are located at opposite ends of the solid-state lithium-containing battery 10. During operation of the solid-state lithium-containing battery 10, when lithium ions flow from the electrode 12 through the solid electrolyte 14 to the second electrode 40, the current collectors 42, 44 facilitate the transfer of electrons to and from the electrodes 12, 40 to power external devices. Alternatively, one or both of the electrodes may be used as current collectors in addition to being electrodes.
[0128] The modified intermediate layer 16 serves as a continuous transmission path for lithium ions between the solid electrolyte 14 and the electrode 12, ensuring high lithium ion conductivity. The viscoelasticity of the modified intermediate layer 16 enables it to maintain close contact between the solid electrolyte 14 and the modified intermediate layer 16 and between the modified intermediate layer 16 and the electrode 12 during severe lithium volume changes of the electrode 12 (e.g., expansion and contraction of the electrode 12). In various aspects, during the cycle of the solid-state lithium-containing battery 10, a portion of the modified intermediate layer 16 also enters the pores of the solid electrolyte 14 and retracts therefrom. Alternatively, a portion of the modified intermediate layer 16 can be in the pores of the solid electrolyte 14 during the entire cycle of the solid-state lithium-containing battery 10 to ensure continuous, close contact and ion transport therebetween. In addition, the viscoelasticity of the modified intermediate layer 16 allows the inclusion of a second electrode 40 (e.g., a cathode) with a relatively high load and higher capacity lithium deposition and stripping at the electrode 12, as shown in the embodiments of this article.
[0129] Without the modified intermediate layer 16, the contact area between the solid electrolyte 14 and the electrode 12 (as a solid-solid interface) will be more limited, resulting in the formation of lithium dendrites at the interface and reducing the critical current density. The limited contact area is further exacerbated by the pulverization and formation of pores by the lithium metal on the electrode 12 during the cycling of the solid-state lithium-containing battery 10. Adding the modified intermediate layer 16 can suppress the occurrence of these problems.
[0130] During use of the solid-state lithium-containing battery 10, the sulfonic acid framework additive 22 and its reaction products (such as LiF and -SO3Li) accumulate at the interface between the modified intermediate layer 16 and the electrode 12 and the interface between the modified intermediate layer 16 and the solid electrolyte 14. This accumulation helps to transfer lithium ions between the interfaces, thereby achieving more uniform lithium ion deposition and movement. In addition, the cross-linking solvent 32 present in the pores 24 of the three-dimensional polymer framework 18 of the modified intermediate layer 16 is believed to improve its lithium ion transport and ability to inhibit lithium dendrites. These properties help to inhibit the formation of lithium dendrites, which may be formed due to uneven deposition and dissolution of lithium ions on the electrode 12 during charge and discharge cycles. The modified intermediate layer 16 makes the deposition and dissolution of lithium ions on the electrode 12 more uniform during these cycles, thereby inhibiting the formation of lithium dendrites and improving the critical current density of the solid-state lithium-containing battery 10.
[0131] The modified intermediate layer 16 disclosed in the present invention shows better results than the strategies reported so far for suppressing lithium dendrites. For example, some strategies propose to use lithium ion conductive polymer-lithium salt (such as polyvinylidene fluoride (PVDF), malononitrile (SCN) or polyethylene glycol (PEO) and LiTFSI) in a polymer matrix and a lithium-philic layer (such as Au, Al, Si, graphite, Al2O3, Li3N, SnF2, Cu3N, etc.) to reduce the interfacial impedance and suppress the formation of lithium dendrites. However, these strategies still have the problem that the interfacial layer has low lithium ion conductivity at room temperature, high interfacial impedance, or insufficient ability to suppress lithium dendrites.
[0132] Therefore, the solid-state lithium-containing battery 10 having the modified intermediate layer 16 of the present disclosure exhibits excellent performance. Specifically, the solid-state lithium-containing battery 10 exhibits 3.5 mA / cm 2 Up to 5.5mA / cm 2 The critical current density range is 3.5 mA / cm. The critical current density refers to the maximum current density that the solid-state lithium-containing battery 10 can withstand without causing damage or degradation to the solid electrolyte 14 or other components. The critical current density of the solid-state lithium-containing battery 10 can be 3.5 mA / cm 2 , 4.0mA / cm 2 , 4.5mA / cm2, 5.0mA / cm 2 or 5.5mA / cm 2, or within the range defined by any two of these values (e.g., from 4.0 mA / cm 2 To 5.0mA / cm 2 , from 4.5mA / cm 2 To 5.5mA / cm 2 The critical current density can be determined by the current charge-discharge method as described below.
[0133] In addition, the solid-state lithium-containing battery 10 with the modified intermediate layer 16 exhibits good cycle stability. Cycle stability refers to the ability of a battery to be charged and discharged multiple times without a significant decrease in capacity or efficiency. High cycle stability indicates that the modified intermediate layer 16 has a high stability to lithium metal. Unless otherwise stated, the Neware battery test system (Neware CT-4008, Shenzhen, China) was used to cycle at a voltage range of 2.8 to 4.5V at a charge rate of 0.2C and a discharge rate of 0.5C at 25°C. For example, at 25°C, the coulombic efficiency of the solid-state lithium-containing battery 10 in at least 50 charge and discharge cycles is greater than or equal to 90%. In some aspects, the coulombic efficiency of the solid-state lithium-containing battery 10 at 25°C is greater than or equal to 90% in at least 200 charge and discharge cycles. In a further aspect, the coulombic efficiency is greater than or equal to 90% over at least 50 cycles (e.g., at least 200 cycles) at charge and discharge rates of 0.2C, 0.4C, 0.5C, 0.6C, 0.8C, and / or 1C. The coulombic efficiency is the ratio of the actual amount of charge delivered or extracted during one cycle to the theoretical amount of charge that can be delivered or extracted if the battery is operating at 100% efficiency. To determine a value, the solid-state lithium-containing battery 10 is cycled at a specific current and voltage range, and the amount of charge delivered or extracted during each cycle is measured using a coulomb meter. The coulomb meter method involves measuring the current flowing through the solid-state lithium-containing battery 10 and integrating the current over time to determine the amount of charge delivered or extracted. The coulombic efficiency is then calculated as the ratio of the charge actually delivered or extracted to the theoretical charge that can be delivered or extracted if the battery is operating at 100% efficiency.
[0134] Throughout this disclosure, "capacity retention" refers to the percentage of discharge capacity that a solid-state battery can achieve after a predetermined number of cycles using the same charge and discharge cycle in all cycles. As used herein, "no lithium dendrites" means that the battery does not exhibit short circuits or non-ohmic behavior during cycling. In various aspects, the solid-state lithium-containing battery 10 has a capacity retention of 50 or more cycles (at 0.5C or 0.45 mA / cm 2In various aspects, the solid-state lithium-containing battery 10 can maintain a capacity retention rate of 75% or more, about 78% or more, 80% or more, 82% or more, 85% or more, 88% or more, or 90% or more after 200 cycles (at 0.5C or at 0.45 mA / cm 2 The solid-state lithium-containing battery 10 can include a capacity retention rate of 75% or more, about 78% or more, 80% or more, 82% or more, 85% or more, 88% or more, 90% or more. In various aspects, the solid-state lithium-containing battery 10 can withstand 100 cycles or more, 200 cycles or more, 400 cycles or more, 600 cycles or more, 800 cycles or more, or 900 cycles or less of charging and discharging at 2C, wherein the charge and discharge cycle is 30 minutes at 25°C. In various aspects, the solid-state lithium-containing battery 10 can withstand 100 hours or more, 200 hours or more, 300 hours or more, 350 hours or more, 400 hours or more, or 420 cycles or more of charging and discharging at 2C, wherein the charge and discharge cycle is 30 minutes at 25°C.
[0135] Reference now Figure 3 , a method 100 for making a solid-state lithium-containing battery 10 is described herein. The method 100 includes an electrospinning step 102, wherein a three-dimensional polymer framework 18 is prepared by an electrospinning solution 104. The solution 104 includes a polymer 28 and a certain weight percentage of a framework additive 22, which is or contains a sulfonic acid. The electrospun polymer nanofibers 20 include the polymer 28 and the framework additive 22 from the solution 104. The electrospinning solution 104 can include any one or more aspects (e.g., polymer, molecular weight, wt% of framework additive, framework additive) and / or be the same as the solution discussed below with reference to step 118.
[0136] See also Figure 4 , the electrospinning step 102 for preparing the three-dimensional polymer framework 18 can be performed using an electrospinning apparatus 106. The electrospinning apparatus 106 can include a power supply 108, a syringe pump 110, a spinner 112, a charged electrode 114, and a grounded collector 116. The power supply 108 generates a potential difference between the charged electrode 114 and the grounded collector 116, while the syringe pump 110 controls the flow rate of the solution 104 released from the spinner 112. The charged electrode 114, such as a metal plate in the illustrated embodiment, is connected to the high voltage power supply 108, is located opposite the grounded collector 116, and serves as a source of an electrostatic field. The grounded collector 116, which can also be a metal plate, is the target of the electrospinning polymer nanofibers 20. Other electrospinning setups can also be used to perform the electrospinning step 102.
[0137] In the electrospinning step 102, the solution 104 is attracted by the electrostatic field generated by the power source 108 from the spinner 112 toward the grounded collector 116. As the solution 104 moves through the electrostatic field, the polymer 28 chains in the solution 104 extend and align with the direction of the electrostatic field, while the solvent in the solution 104 evaporates. As the solvent evaporates, the viscosity of the solution 104 increases, causing the polymer chains to entangle together, thereby forming electrospun polymer nanofibers 20. These electrospun polymer nanofibers 20 are collected on the grounded collector 116 and form a three-dimensional polymer framework 18. In various aspects, the molecular weight (Mn) of the polymer 28 in the solution 104 used to form the electrospun polymer nanofibers can be within any of the corresponding ranges of the molecular weights of the polymer nanofibers 20 discussed above.
[0138] In some aspects, the method 100 further includes a solution preparation step 118 that occurs before the electrospinning step 102. In the solution preparation step 118, the polymer 28 and the desired ratio of the framework additive 22 are dissolved in the solvent to form the solution 104. The polymer 28 used in this step can be any of the previously mentioned ones, which form the polymer matrix of the electrospun polymer nanofibers 20 of the three-dimensional polymer framework 18. This step can ensure consistent and uniform mixing of the polymer and the framework additive, thereby making the electrospinning process more reliable and the quality of the three-dimensional polymer framework 18 higher.
[0139] The weight percentage of the framework additive 22 in the solution 104 can be in the range of 0.10 wt% to 3.0 wt%. For example, 0.25 wt% to 2.5 wt%, 0.5 wt% to 2 wt%, 0.5 wt% to 1.5 wt%, 0.5 wt% to 1.25 wt%, 0.5 wt% to 1 wt%, or any range or sub-range therebetween. In various aspects, the weight percentage of the framework additive 22 is 0.10 wt%, 0.25 wt%, 0.5 wt%, 0.75 wt%, 1.0 wt%, 1.25 wt%, 1.50 wt%, 1.75 wt%, 2.0 wt%, 2.25 wt%, 2.50 wt%, 2.75 wt% or 3.0 wt%, or in any range determined by any two limits between these values (e.g., from 0.75 wt% to 1.50 wt%, from 1.0 wt% to 2.0 wt%, etc.). The weight percentage of the framework additive 22 in the solution 104 may be less than 0.10 wt % or greater than 3.0 wt %.
[0140] As previously described, the framework additive 22 is or comprises a sulfonic acid, and may be any of those previously discussed, such as D(+)-10-camphorsulfonic acid (DCA). The presence of the sulfonic acid plays a key role in the electrospinning step 102 and the performance of the three-dimensional polymer framework 18. In the electrospinning step 102, the presence of the sulfonic acid enhances the electrospinning ability of the polymer 28 in the solution, thereby obtaining more uniform electrospun polymer nanofibers 20 with a diameter range of 10 nm to 50 nm and minimal nodules. This increased uniformity of the electrospun polymer nanofibers 20 ultimately results in improved lithium ion conductivity at the interface between the modified intermediate layer 16, the electrode 12, and the solid electrolyte 14.
[0141] See also Figure 5 , the method 100 further includes a contacting step 120, in which the three-dimensional polymer framework 18 is contacted with a monomer reaction mixture 122 containing a cross-linking monomer or prepolymer, a cross-linking solvent 32, and a lithium salt 34. The monomer reaction mixture 122 can be prepared in a container 124. Then, the three-dimensional polymer framework 18 is placed in the container 124 and immersed in the monomer reaction mixture 122. Alternatively or additionally, although not shown, the monomer reaction mixture 122 can be dripped (e.g., added dropwise) from the container 124 onto the three-dimensional polymer framework 18. In any case, during the contacting step 120, the monomer reaction mixture 122 enters the pores 24 between the electrospun polymer nanofibers 20 of the three-dimensional polymer framework 18. In some aspects, during the contacting step 120, the absorption rate (η) of the three-dimensional polymer framework 18 to the monomer reaction mixture 122 is greater than or equal to 800% or greater than or equal to 900%. The absorption rate (η) is calculated as η=100%×(M wet -M dry ) / M dry , where M dry is the initial mass of the three-dimensional polymer framework, M wet is the mass of the three-dimensional polymer framework 18 after being in contact with the monomer reaction mixture 122 for 2 hours.
[0142] In some aspects, the amount of monomer reaction mixture 122 held (ie, absorbed) by the three-dimensional polymer framework 18 may be about 3 μL / cm 2 or more, about 6μL / cm 2 More, about 13μL / cm 2 Or more, about 19μL / cm 2 More, about 26μL / cm 2 More, about 60μL / cm 2 Lower, about 45μL / cm 2 Lower, about 40μL / cm 2 Lower, 35μL / cm 2or about 30 μL / cm 2 Lower, about 26μL / cm 2 Lower, or about 20 μL / cm 2 In various aspects, the amount of monomer reaction mixture 122 held (ie, absorbed) by the three-dimensional polymer framework 18 may be in the range of from about 3 μL / cm 2 to about 60 μL / cm 2 , from about 3μL / cm 2 or to about 40 μL / cm 2 , from about 6μL / cm 2 To about 35μL / cm 2 , from about 13μL / cm 2 To 30μL / cm 2 , from about 13μL / cm 2 to about 26 μL / cm 2 and about 13 μL / cm 2 To about 20μL / cm 2 or any range or sub-range therebetween.
[0143] In some aspects, the molecular weight (Mn) of the cross-linkable monomer or prepolymer in the monomer reaction mixture 122 can be about 500 Da or more, about 700 Da or more, about 800 Da or more, about 900 Da or more, about 10,000 Da or less, about 4,000 Da or less, about 2,000 Da or less, about 1,500 Da or less, or about 1,000 Da or less. In various aspects, the molecular weight (Mn) of the cross-linkable monomer or prepolymer in the monomer reaction mixture 122 can be in the range of about 500 Da to about 10,000 Da, about 700 Da to about 4,000 Da, about 800 Da to about 2,000 Da, about 900 Da to about 1,500 Da, or any range or sub-range therebetween.
[0144] In some aspects, the amount of the cross-linkable monomer or prepolymer, as a percentage of the weight of the monomer reaction mixture 122, can be about 3 wt% or more, about 5 wt% or more, about 7 wt% or more, about 9 wt% or more, about 20 wt% or less, about 18 wt% or less, about 15 wt% or less, or about 12 wt% or less. In various aspects, the amount of the cross-linkable monomer or prepolymer, as a percentage of the weight of the monomer reaction mixture 122, can be in the range of about 3 wt% to about 20 wt%, about 5 wt% to about 18 wt%, about 7 wt% to about 15 wt%, about 9 wt% to about 12 wt%, or any range or sub-range therebetween.
[0145] In some aspects, the median diameter of the electrospun polymer nanofibers 20 of the three-dimensional polymer framework 18 can be about 10 nm or more, about 12 nm or more, about 15 nm or more, about 17 nm or less, about 20 nm or less, about 50 nm or less, about 40 nm or less, about 30 nm or less, about 25 nm or less, or about 20 nm or less. In various aspects, the median diameter of the electrospun polymer nanofibers 20 can be in the range of about 10 nm to about 50 nm, about 12 nm to about 40 nm, about 15 nm to about 30 nm, about 17 nm to about 25 nm, or any range or sub-range therebetween. In various aspects, 50% or more, 60% or more, 70% or more, or 80% or more of the diameter distribution of the electrospun polymer nanofibers 20 can be approximately within one or more ranges of the median diameters described above in this paragraph.
[0146] In the monomer reaction mixture 122, the crosslinkable monomer or prepolymer may be an alcohol-containing acrylate, an alcohol-containing methacrylate, ethylene carbonate, or a polymer, copolymer, or derivative thereof. For example, the crosslinkable monomer or prepolymer may be selected from those mentioned above, such as diethylene glycol diacrylate (DEGDA), diethylene glycol dimethacrylate (DEGDMA), vinyl ethylene carbonate (VEC), etc., to provide the necessary units of the crosslinked polymer network of the crosslinked polymer 30 for modifying the intermediate layer 16. In addition, the monomer reaction mixture 122 may include fluorinated organic compounds (e.g., fluoroethers), such as polyperfluoromethyl isopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), fluorobenzene (FB). These fluorinated organic compounds may be incorporated into the crosslinked polymer 30 formed in the pores 24 of the three-dimensional polymer framework 18. Among the other advantages mentioned above, the use of fluorinated organic compounds can increase the critical current density of the modified interlayer 16 , which improves the performance of the solid-state lithium-containing battery 10 .
[0147] The crosslinking solvent 32 may include any of the previously mentioned solvents, such as fluoroethylene carbonate (FEC), vinyl carbonate (VC) and other similar solvents. These solvents can dissolve the crosslinking monomers or prepolymers to form a network structure of crosslinked polymers 30 in the pores 24 of the three-dimensional polymer framework 18.
[0148] In some aspects, the amount of the fluorinated organic compound, based on the weight percent of the monomer reaction mixture 122, can be about 1.5 wt% or more, about 2 wt% or more, about 2.5 wt% or more, about 4.5 wt% or more, about 18 wt% or less, about 12 wt% or less, about 9 wt% or less, or about 6 wt% or less. In various aspects, the amount of the fluorinated organic compound, based on the weight percent of the monomer reaction mixture 122, can be in the range of about 1.5 wt% to about 18 wt%, about 1.5 wt% to about 12 wt%, about 2 wt% to about 9 wt%, about 2.5 wt% to about 6 wt%, or any range or sub-range therebetween.
[0149] Similarly, the lithium salt 34 can improve the ionic conductivity of the cross-linked polymer 30, thereby improving the ionic conductivity of the modified intermediate layer 16, including any of the aforementioned, such as lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalate (LiDFOB), LiFSI or LiTFSI, etc. The lithium salt 34 can be dissolved in the cross-linking solvent 32 and uniformly dispersed in the matrix of the cross-linked polymer 30 in the pores 24 of the three-dimensional polymer framework 18. In various aspects, the amount of the lithium salt, as a concentration in the monomer reaction mixture, can be about 1 molar (mol / L, M) or greater, about 2M or greater, about 3M or greater, about 4M or greater, about 8M or less, about 7M or less, about 6M or less or about 6M or less, for example, in the range of about 1M to about 8M, about 2M to about 7M, about 3M to about 6M, from about 4M to about 6M or any range or sub-range therebetween.
[0150] In some aspects, the monomer reaction mixture 122 contains an initiator, which is used to initiate the crosslinking of a crosslinkable monomer or prepolymer. In further aspects, the initiator can be a photoinitiator, although the initiator can be a thermal initiator as described below. For example, when the method proceeds to step 126 (opposite to following arrow 131 to step 132), a photoinitiator can be provided in the monomer reaction mixture. The photoinitiator is configured to produce one or more free radicals or ions that can start a crosslinking reaction when the photoinitiator is irradiated with a wavelength sensitive to the photoinitiator. Some suitable photoinitiators for the monomer reaction mixture 122 include 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP), methyl benzoylformate (MBF), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methyl-acrylate, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (TPO), 2-methyl-4'-(methylthio)-2-morpholinyl-benzoin and 1-hydroxycyclohexyl phenyl ketone, etc. This list of photoinitiators is not exclusive, and other photoinitiators may be used.
[0151] Alternatively, in a further aspect, the initiator may include a thermal initiator. For example, when the method proceeds to step 132 (opposite to proceeding to step 126) according to arrow 131, a thermal initiator may be provided in the monomer reaction mixture. The thermal initiator is configured to generate one or more free radicals or ions, and when the thermal initiator is heated at a temperature equal to or greater than a predetermined temperature, the free radicals or cations may start a crosslinking reaction. Some suitable thermal initiators for use in the monomer reaction mixture 122 include 2,2'-azobis(2-methylpropionitrile) (AIBN), 2,2'azobis(2,4-dimethylvaleronitrile) (AVBN) and azobis(dimethylpentacrylonitrile) (AMVN), 2'-azobis(2-methylpropionic acid) dimethyl ester, 2,2'-nitrobis[2-(2-imidazoline-2-yl)-propane] dihydrochloride, cumene peroxide, and di-tert-butyl peroxide.
[0152] In a further aspect, the concentration of the initiator (e.g., photoinitiator, thermal initiator), as a weight percent of the amount of the crosslinkable monomer or prepolymer, can be about 0.1 wt% or more, about 0.25 wt% or more, about 0.4 wt% or more, about 0.5 wt% or more, about 1 wt% or less, about 0.75 wt% or less, about 0.6 wt% or less. In a further aspect, the concentration of the initiator (e.g., photoinitiator, thermal initiator), as a weight percent of the amount of the crosslinkable monomer or prepolymer, can be in the range of about 0.1 wt% to about 1 wt%, about 0.25 wt% to about 0.75 wt%, about 0.4 wt% to about 0.6 wt%, or any range or sub-range therebetween.
[0153] See also Figure 6 After step 120, method 100 further includes a crosslinking step 126, in which the crosslinkable monomer or prepolymer is crosslinked in the monomer reaction mixture 122. This forms a modified intermediate layer 16 (see Figure 2 ), wherein the crosslinkable monomers or prepolymers of the monomer reaction mixture 122 become crosslinked polymers 30 in the pores 24 of the three-dimensional polymer framework 18. The crosslinking solvent 32 and the lithium salt 34 are also distributed in the matrix of the crosslinked polymer 30 in the pores 24 of the three-dimensional polymer framework 18 from the monomer reaction mixture 122. In some aspects, ultraviolet light 128 is used to promote crosslinking of the crosslinkable monomers or prepolymers of the monomer reaction mixture 122.
[0154] review Figure 1 , the method 100 further includes an assembly step 130 after the cross-linking step 126. The assembly step 130 includes placing the modified intermediate layer 16 between the electrode 12 and the solid electrolyte 14. Once the modified intermediate layer 16 is properly placed, the remaining components of the solid-state lithium-containing battery 10 can be assembled.
[0155] Alternatively, after step 120, method 100 may proceed as shown in arrow 131 (see Figure 3 ) proceeds to assembly step 132, such as Fig.12 As shown. As shown, the assembly step 132 includes disposing an interlayer precursor 1211 including a monomer reaction mixture 122 and a three-dimensional polymer framework 18 on the solid electrolyte 14. In various aspects, as schematically shown, this arrangement can allow the interlayer precursor 1211 to penetrate the pores 1203 of the solid electrolyte 14, so that a portion of the interlayer precursor 1211 (e.g., the monomer reaction mixture 132) is located in the pores 1203 in the solid electrolyte 14. In various aspects, as shown, the assembly step 132 can further include disposing the first electrode 12 or a precursor (e.g., a lithium metal foil) on the interlayer precursor 1211, so that the interlayer precursor is positioned between the first electrode 12 and the solid electrolyte 14.
[0156] After step 132, if Fig.12 As further shown, the method 100 can proceed to a crosslinking step 134, including heating the interlayer precursor 1211. As shown, the interlayer precursor 1211, the solid electrolyte 14, and the first electrode 12 can be heated in an oven 1201 maintained at a predetermined temperature for a predetermined period of time. Heating the interlayer precursor 1211 in step 134 can activate the thermal initiator and crosslink the crosslinkable monomers or prepolymers of the monomer reaction mixture 122. In various aspects, the predetermined period of time can be about 10 minutes or more, 0.5 hours or more, about 1 hour or more, about 1.5 hours or more, about 2 hours or more, about 8 hours or less, about 4 hours or less, about 3 hours or less, about 2.5 hours or less, or about 2 hours or less. In various aspects, the predetermined period of time can be in the range of about 10 minutes to about 8 hours, about 0.5 hours to about 8 hours, about 1 hour to about 4 hours, about 1.5 hours to about 3 hours, or in any range or sub-range therebetween. In various aspects, the predetermined temperature may be about 50° C. or more, about 55° C. or more, about 60° C. or more, about 65° C. or more, about 70° C. or more, about 120° C. or less, about 100° C. or less, about 90° C. or less, about 80° C. or less, about 75° C. or less, or about 70° C. In various aspects, the predetermined temperature may be in a range from about 50° C. to about 120° C., from about 55° C. to about 100° C., from about 60° C. to 80° C., from about 65° C. to about 75° C., or any range or sub-range therebetween. At the end of step 130 or 134, method 100 may be completed.
[0157] One of the main advantages of the method 100 is the speed of its steps. All steps including the solution preparation step 118, the electrospinning step 102, the contacting step 120, the cross-linking step 126, and the assembly step 130 can be performed quickly. In addition, the cross-linking monomers or prepolymers used to prepare the three-dimensional polymer framework 18 and the monomer reaction mixture 122 can be obtained at a relatively low cost.
[0158] Example
[0159] Various aspects will be further illustrated by the following examples. Examples 1-7 and Comparative Examples 1-2 include a LLZT-2LWO solid electrolyte (described below) and a lithium metal electrode (e.g., an anode). In Examples 1-4, 6, and Comparative Examples 1-2, the solid electrolyte was polished with 1200 mesh SiC sandpaper to obtain a smooth surface ("SiC"). In contrast, the solid electrolytes in Examples 5 and 7 were etched with a 2 molar HCl solution for 1 minute ("etching"). Comparative Example 2 does not include a modified interlayer between the lithium metal and the solid electrolyte. For Examples 1-7 and Comparative Example 1, a modified interlayer including a PVDF-HFP electrospinning polymer and a cross-linked polymer is placed between the lithium metal and the solid electrolyte. The amount of DCA used in the electrospinning solution varies: 0 wt% in Comparative Example 1; 0.25 wt% in Example 3; 0.5 wt% in Example 2; 1 wt% in Examples 1 and 5-7; and 2 wt% in Example 4. For Examples 1-5 and Comparative Example 1, the crosslinked polymer includes a methacrylate polymer formed by curing poly(ethylene glycol methyl ether methacrylate) (PEGMEMA) using ultraviolet light (UV) and using a photoinitiator (HMPP). For Examples 6-7, the crosslinked polymer includes a polymer formed by curing a ethylene carbonate prepolymer (ethylene ethylene carbonate) by heating at 70°C for 2 hours using a thermal initiator (AIBN). Table 1 shows the characteristics of the symmetrical cells assembled for Examples 1-2 and 5-7 and Comparative Example 2. Table 2 shows the characteristics of the full cells assembled for Examples 1*, 6* and 7* and Comparative Example 2. Examples 1*, 6* and 7* correspond to Examples 1, 6 and 7, respectively, except that an NCM cathode and an electrolyte between the NCM cathode and the solid electrolyte are used. Comparative Example 2* corresponds to Comparative Example 2, except that an NCM cathode and an electrolyte between the NCM cathode and the solid electrolyte are used.
[0160] UV-curable modified interlayer containing methacrylate
[0161] Example 1 (1.0% DCA) - In Example 1, a solution preparation step was performed to form a solution for the subsequent electrospinning step. Poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) and D(+)-10-camphorsulfonic acid (DCA) were dissolved in N,N-dimethylformamide (DMF). The molecular weight of the PVDF-HFP used was approximately 400,000 Da. The weight percentage of DCA was 1.0% based on the weight of PVDF-HFP. The mixture was stirred for 12 hours to achieve uniformity before proceeding to the electrospinning step.
[0162] The electrospinning step was performed using an electrospinning device (ET-2535H) with an operating voltage of 8 kV, a working distance of 16 cm, and a propulsion speed of 0.3 mL / h. The solution was electrospun to form a three-dimensional polymer framework containing electrospun polymer nanofibers and pores between them. SEM images of electrospun polymer nanofibers were taken using a Hitachi S-3400N scanning electron microscope (SEM), as shown in Figure 7 As shown in Figure 2, the diameter of electrospun polymer nanofibers is between 10nm and 50nm. Figure 8 The cross-sectional SEM image of the 3D polymer framework showed a thickness of 38 μm.
[0163] After the electrospinning step, the resulting 3D polymer framework was dried in a vacuum oven at 70 °C for 24 h, then cut into discs with a diameter of 14 mm and quickly transferred to a glove box. This step ensures that the 3D polymer framework is not affected by air and moisture, which may affect its performance as a modified interlayer in solid-state lithium metal batteries.
[0164] To prepare the monomer reaction mixture, poly(ethylene glycol methyl ether methacrylate) (PEGMEMA) was used as a cross-linking prepolymer, fluoroethylene carbonate (FEC) was used as a cross-linking solvent, and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was used as a lithium salt. First, 10 wt.% PEGMEMA monomer with a molecular weight of Mn~950Da was sealed and stirred with 5 mol / L (M) LiTFSI in a fluoroethylene carbonate (FEC, 99%) solution for 2 hours. Then, the resulting solution was stirred with polyperfluoromethyl isopropyl ether (PFPE) at a weight ratio of ~40:1 (~2.44 wt%) for another 2 hours. Prior to the cross-linking step, 0.5 wt.% 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) photoinitiator was added to the monomer reaction mixture, and the HMPP weight was based on the weight of the PEGMEM prepolymer.
[0165] The contacting step was performed by dropping the monomer reaction mixture onto a sample of the three-dimensional polymer framework. Approximately 20 μL (13 μL / cm2 ) is dripped onto the surface of the three-dimensional polymer framework.
[0166] Under dry conditions, weigh the mass (M) of a circular three-dimensional polymer framework sample with a diameter of 16 mm. dry ). Then, the sample was immersed in the monomer reaction mixture in the glove box for 2 hours. After removing any excess mixture on the surface with filter paper, the mass was recorded as M wet Due to its high porosity, the absorption rate (η) of the three-dimensional polymer framework is 920%.
[0167] Then, a cross-linking step is performed in the three-dimensional polymer framework, wherein the added monomer reaction mixture has infiltrated the pores. The cross-linking prepolymer of the monomer reaction mixture is cross-linked using a 365 nm mercury ultraviolet lamp.
[0168] Next, the three-dimensional polymer framework is subjected to a cross-linking step. The cross-linking prepolymer of the monomer reaction mixture is cross-linked in the pores of the three-dimensional polymer framework using a 365nm mercury ultraviolet lamp. In this step, the cross-linking prepolymer of the monomer reaction mixture is converted into a cross-linked polymer to form a matrix in the pores of the three-dimensional polymer framework. In this way, a stable and mechanically strong modified interlayer is formed.
[0169] Fig. 9 and Fig.10 The SEM images of the surface and cross section of the modified interlayer are shown in Figures 2 and 3. The thickness of the modified interlayer is 40 μm, and the cross-linked polymers in the pores of the three-dimensional polymer framework lead to an increase of 2 μm in thickness compared to the three-dimensional polymer framework before the addition of the monomer reaction mixture. Fig.10 As shown in the cross-sectional view, the cross-linked polymer completely fills the pores of the three-dimensional polymer framework.
[0170] Various mechanical properties of the modified interlayer were measured. For example, a torque was applied to the modified interlayer and then released. The modified interlayer exhibited minimal deformation due to the torsional force and recovered to its original shape after the torsional force was released. Optical images of the modified interlayer after applying the torque and releasing the torque were shown in Figure 2. Fig.11 As shown, the modified interlayer recovers to its original shape after releasing the torque.
[0171] The thickness of the modified interlayer in the uncompressed and compressed states was measured using a vernier caliper. The optical images of the two measurement results are shown in Figure 2. Fig.12 As shown, the modified interlayer in the uncompressed state and the compressed state is 40 μm and 10 μm, respectively. The modified interlayer has elastic, flexible and deformable properties, which is very important to ensure good contact with the solid electrolyte interface.
[0172] The electrochemical performance of the modified interlayer was also studied. The Nyquist plots of the modified interlayer were tested at different temperatures (see Fig.13 ). The Nyquist plot is a graph of imaginary impedance (Z") and real impedance (Z'). The Nyquist plot in the present disclosure is obtained by performing AC impedance analysis using Metrohm Autolab (PGSTAT302 N) in a frequency range of 0.1 Hz to 1 MHz.
[0173] In addition, the ionic conductivity of the modified interlayer was measured. The results showed that at 60 °C, the ionic conductivity of the modified interlayer was 16.09×10 -4 S / cm, while at 30°C it is 6.15×10 -4 S / cm. Both values are considered high. The modified interlayer was sandwiched between two stainless steel plates and sealed in a CR2025 button cell and measured using a Metrohm Autolab (PGSTAT302 N) with a frequency range of 1 Hz to 1 MHz.
[0174] A solid-state lithium metal symmetric battery is assembled. The solid-state lithium metal symmetric battery includes a solid electrolyte, which is LLZT-2LWO and a modified intermediate layer.
[0175] In order to prepare the solid electrolyte, precursor powders such as LiOH·H2O (analytical pure, excess 2%), La2O3 (99.99%, calcined at 900℃ for 12 hours), ZrO2 (analytical pure) and Ta2O5 (99.99%) were prepared by Li 6.5 LqCy 1.5 Ta 0.5 O 12 The stoichiometric ratio of 200 μL was weighed and mixed. Isopropyl alcohol was used as solvent and yttrium-stabilized zirconia balls were used as grinding media for wet ball milling in a planetary ball mill for 12 h. The obtained powder was then calcined in an aluminum crucible at 950 °C for 6 h to obtain pure cubic lithium garnet electrolyte (LLZT) powder.
[0176] The Li2WO4 (LWO) component of the composite electrolyte was prepared by weighing LiOH·H2O (AR) and WO3 (AR) in a molar ratio of 2:1. Isopropyl alcohol was used as the solvent and the reaction mixture was heated at 250 rpm min -1 The obtained dry mixture was then calcined in an aluminum crucible at 500 °C for 2 h to obtain pure LWO powder.
[0177] To prepare the LLZT-2LWO composite electrolyte, LLZT powder and LWO powder were weighed in a certain ratio (100:2 wt%). Then, the mixture was heated at 250 rpm min -1The powder was wet-milled using a solvent at a rotation speed of 100°C for 12 hours. After that, the mixture was dried at 70°C for 12 hours and passed through a 200-mesh sieve to obtain fine particles. Then, the fine particles were pressed into green blanks using a uniaxial pressure of 100MPa. The green blank discs had a diameter of 18mm and each weighed 1.25g. Then, the green blank discs were placed in a platinum crucible and sintered at 1190°C for 30 minutes to obtain LLZT-2LWO. Finally, all LLZT-2LWO were polished with 400-mesh, 800-mesh and 1200-mesh SiC sandpaper to obtain a smooth surface for better contact with the modified interlayer.
[0178] A solid-state lithium metal symmetric cell was assembled, and then a modified interlayer was placed directly between the surface of LLZT-2LWO and the lithium sheet. An additional modified interlayer was placed on the other surface of LLZT-2LWO, and another lithium sheet was placed on the additional modified interlayer. These assemblies were then sealed in a CR2025 button cell. To prevent the effects of H2O and O2, the assembly process was carried out in an argon-filled glove box with H2O and O2 levels below 0.1ppm.
[0179] The critical current density test of the solid-state lithium metal symmetric battery was carried out to determine the maximum current density that the battery can withstand. The battery was repeatedly charged and discharged at increasing current density (0.2 mA / cm 2 The step size ranges from 0.2 to 6 mA / cm 2 ) until a critical point is reached. The critical point is the point at which the battery fails or shows significant performance degradation, indicating that the maximum safe current density has been exceeded. The highest current density at which the battery can maintain performance and capacity without significant performance degradation or battery failure is defined as the critical current density (CCD). Fig.14 As shown, the voltage and current density are plotted as a function of time during the test. The critical current density test shows that the critical current density of the solid-state lithium metal symmetric battery assembled using the modified interlayer can exceed 4.0 mA / cm 2 .
[0180] In addition, long-term constant current cycling tests were performed on solid-state lithium metal symmetric batteries to evaluate their long-term cycling stability and capacity retention. Fig.15 As shown, the voltage is plotted against time to show the stable performance of the battery in the long-term constant current cycle test. 2The constant current was used for more than 420 hours of charge and discharge cycles, with each charge and discharge test lasting 30 minutes. The test results show that the solid-state lithium metal symmetric battery assembled using the modified intermediate layer has excellent cycle stability and high stability to lithium (such as lithium ions, lithium metal) at higher current density. In addition, after 420 hours of testing, no sudden voltage drop was observed, indicating that the modified intermediate layer has excellent ability to inhibit dendrite growth.
[0181] In addition, a deposition experiment was also conducted on solid-state lithium metal symmetric batteries, where the 2 The current density is charged for 3 hours, reaching 3mAh / cm 2 The surface capacity of the lithium sheet after cycling was analyzed by SEM and EDS to determine the morphology of the lithium sheet and the distribution of sulfur (S), oxygen (O) and fluorine (F) atoms. Fig.16 As shown, SEM images and EDS analysis results are plotted. EDS analysis shows the presence of S, O, and F atoms on the surface of the lithium sheet, indicating the presence of DCA and its reaction products (such as LiF and -SO3Li) on the surface of the lithium sheet. -SO3Li with higher lithium ion conductivity can further inhibit the formation of lithium dendrites and increase the critical current density.
[0182] For further testing, solid-state lithium metal full batteries (Example 1# and Example 1*) were constructed. 0.6 Co 0.2 Mn 0.2 The method for assembling a full cell with an O2(NCM) cathode is as follows. First, a modified interlayer is placed between LLZT-2LWO and the lithium sheet to improve interfacial contact and cycling stability. Secondly, on the cathode side, a small amount of liquid electrolyte (LiTFSI and cyclopentane sulfone (TMS) electrolyte, with a molar ratio of 1:3) is dripped on the cathode interface to obtain good interfacial contact. All steps are carried out in an argon-filled glove box with H2O and O2 levels below 0.1ppm to minimize the impact of H2O and O2. Then, these components are assembled in CR2025 button cells for testing.
[0183] Two such solid-state lithium metal full cells were constructed with different cathode loadings. The first cell (Example 1#) had 3 mg / cm 2 The cathode has a nickel-cobalt-manganese (NCM) loading of 21 mg / cm 2 The higher NCM loading is believed to increase the energy density of the battery. The performance of the two batteries was evaluated through a series of tests, as described below.
[0184] Solid-state lithium metal full cells are subjected to rate performance testing to evaluate their ability to provide discharge capacity at different discharge or charge rates. The discharge or charge rate of a battery is represented by its C, and during the test, the battery undergoes a series of charge and discharge cycles at different Cs (0.2C, 0.4C, 0.8C, 1C, and 0.2C again). The voltage and specific capacity of the battery are measured during the test to evaluate its performance and stability. Specific capacity refers to the amount of energy that can be stored in a battery per unit mass or volume, and is an important indicator of battery performance.
[0185] For 3mg / cm 2 The solid-state lithium metal full battery loaded with NCM cathode (Example 1#) was tested for rate performance and cycle stability. The change of specific capacity and coulombic efficiency percentage with cycle number and rate is shown in Fig.17 The voltage changes with specific capacity and rate as shown in Fig.18 The discharge capacities of the battery at 0.2C, 0.4C, 0.8C and 1.0C rates were 177.7, 165.4, 145.1 and 133.8 mAh / g, respectively, showing good performance. A cycle test with a current density of 0.5C was also conducted, and the results are shown in Fig.19 and Fig. 20 At the end of 200 cycles, the battery maintained 133.7 mAh / g (0.35 mAh / cm 2 ) with no apparent capacity decay (about 80% capacity retention).
[0186] In addition, it also demonstrated a 21mg / cm 2 Test results of solid-state lithium metal full battery loaded with NCM cathode (Example 1*). Long-term cycle test at 0.45 mA / cm 2 The current density was 2.8 to 4.5 V. Fig.21 The relationship between the specific capacity and coulombic efficiency of the battery. As shown in the figure, the battery is at 0.45mA / cm 2 The current density of 3.16 mAh / cm2 was still maintained after 50 cycles. 2 discharge capacity. Fig. 22 The figure is the relationship between voltage, specific capacity and rate, showing the stable charge and discharge curve. In addition, the Nyquist plot is also measured to characterize the interface resistance in the battery. Fig.23 As shown, the interfacial impedance of the battery is about 304Ωcm 2 .
[0187] All solid-state lithium metal symmetric cells and full cells were tested using a Neware battery test system (NEWARE CT-4008, Shenzhen, China). The Neware CT-4008 is a high-precision battery test instrument capable of testing a variety of battery chemistries.
[0188] Example 2 (0.5 wt % DCA) - Example 2 is identical to Example 1, except that the content of D(+)-10-camphorsulfonic acid in the solution used in the preparation step is 0.5 wt %, instead of 1.0 wt % in Example 1. Fig.24 The impedance test results of the modified interlayer at different temperatures are shown. By comparing the Nyquist plot of the modified interlayer prepared by the solution containing 1.0 wt% DCA in Example 1 ( Fig.13 ) and the Nyquist plot of the modified intermediate layer prepared from the solution containing 0.5 wt % DCA in Example 2 ( Fig.24 ), it can be observed that the modified intermediate layer prepared in Example 2 has lower impedance at low temperatures.
[0189] The ionic conductivity of the modified interlayer was measured to evaluate its ability to promote ion transport between the lithium anode and the solid electrolyte. The measurements were performed at two different temperatures: 30°C and 60°C. The ionic conductivity of Example 2 was higher, at 6.92×10 -4 S / cm, at 60°C: 14.96×10 -4 S / cm. These high values indicate that the modified interlayer can effectively promote ion transport, thereby improving battery performance and stability.
[0190] In order to evaluate the effectiveness of the modified intermediate layer of Example 2, a solid-state lithium metal symmetrical battery was assembled using the same assembly method as described in Example 1 and the critical current density test of the battery was tested to test the stability of the battery under high current density conditions. Fig.25 The results show that the critical current density of the battery with the modified interlayer is about 4.6 mA / cm 2 , which is significantly higher than the critical current density of the battery without the modified interlayer (see Comparative Example 2 below). This shows that the modified interlayer effectively suppresses the formation of lithium dendrites and enables the battery to operate at a high current density.
[0191] Example 3 (0.25 wt% DCA) - Example 3 was conducted to investigate the effect of a lower concentration of D(+)-10-camphorsulfonic acid (DCA) on the modified interlayer. Similar to Examples 1 and 2, Example 3 involved preparing a modified interlayer but with the DCA content reduced to 0.25 wt%. This concentration variation was intended to explore the effect of DCA concentration on the properties of the modified interlayer.
[0192] The ionic conductivity of the modified interlayer was measured using electrochemical impedance spectroscopy at 30 °C. The measured ionic conductivity was 6.02 × 10 -4 S / cm, which is a relatively high value for solid-state lithium metal batteries. Compared with the previous examples, this value is slightly lower than that in Example 1 (1.0 wt% DCA, 6.14×10 -4 S / cm), but still of the same order of magnitude.
[0193] Example 4 (2.0 wt % DCA) - Example 4 is the same as Example 1, except that in the solution preparation step, the content of D(+)-10-camphorsulfonic acid (DCA) in the solution is 2.0 wt %, instead of 1.0 wt % DCA in Example 1.
[0194] The ionic conductivity of the modified interlayers of Examples 1 to 4 was measured. At 30°C, the ionic conductivity of Example 1 (1.0 wt% DCA) was measured to be 6.15×10 -4 S / cm, the ionic conductivity of Example 2 (0.5 wt% DCA) was measured to be 6.92×10 -4 S / cm, the ionic conductivity of Example 3 (0.25 wt% DCA) was measured to be 6.02×10 -4 S / cm, the ionic conductivity of Example 4 (2 wt% DCA) was measured to be 5.58×10 -4 S / cm. The graph of the ionic conductivity of the modified intermediate layer of Examples 1-4 at 30°C is shown in FIG. Fig.26 It is worth noting that the graph shows that the ionic conductivity is the highest when the DCA content is 0.5wt%, and as the DCA content deviates from this concentration, the ionic conductivity generally decreases.
[0195] Example 5 (1 wt % DCA, etched solid electrolyte) - Example 5 is the same as Example 1 (1 wt % DCA), except that the solid electrolyte is etched with a 2 molar HCl solution for 1 minute to form a porous surface (rather than a smooth surface formed by SiC polishing) ("Etching"). Figure 2 : is a SEM image of an etched solid electrolyte cross section (before forming the modified intermediate layer). As shown in the figure, the pores extend from the surface of the solid electrolyte to a thickness of about 13 μm.
[0196] The solid-state lithium metal symmetric cell assembled from the modified interlayer (1.0 wt% DCA) of Example 5 and the solid electrolyte (etched) exhibited a current of 2.8 mA / cm at 25 °C. 2 The critical current density (CCD) of Example 5 (2.8 mA / cm 2 Compared with the CCD of Example 1 (4.0 mA / cm 2The increase in CCD of ) may be due to the increased contact area between the SiC polished solid electrolyte (Example 1) compared to the etched solid electrolyte (Example 5). Since the modified interlayer is cured before being positioned between the lithium-containing electrode (lithium metal) and the solid electrolyte, the modified interlayer cannot effectively occupy the pores in the etched surface of Example 5. In addition, Example 5 has a CCD of 216 Ωcm 2 This further reinforces the idea that the UV-cured interlayer has better contact with the solid electrolyte when the solid electrolyte is polished and / or non-porous.
[0197] Comparative Examples
[0198] Comparative Example 1 (without DCA) - Comparative Example 1 (CE 1) was prepared according to the same steps as Example 1, except that the solution used in the electrospinning step did not contain any weight percentage of D(+)-10-camphorsulfonic acid (DCA) or other sulfonic acids. SEM images of the resulting electrospun polymer nanofibers were obtained, as shown in FIG. Fig. 27 The image shows that the diameter of the electrospun polymer nanofibers ranges from 100 nm to 200 nm. Comparative Example 1 shows a much larger diameter than the nanofibers spun in the presence of sulfonic acid. The SEM image of Example 1 (with DCA) ( Figure 7 ) and SEM images of Comparative Example 1 (without sulfonic acid) ( Fig. 27 ), it can be found that the addition of DCA in the electrospinning solution results in a smaller fiber diameter compared to the electrospun nanofibers without sulfonic acid. In addition, the electrospun nanofibers prepared from the solution containing DCA show fewer nodules than the nanofibers electrospun without any sulfonic acid.
[0199] A solid-state lithium metal symmetric cell with a modified interlayer without DCA was assembled. The critical current density of the cell was measured to be 3.6 mA / cm at 25 °C. 2 This value is lower than the critical current density obtained in Examples 1-4, which all included a modified interlayer prepared using DCA. These results indicate that the modified interlayer containing DCA not only helps to achieve good interfacial contact between lithium and the solid electrolyte, but also effectively inhibits the formation of lithium dendrites.
[0200] Comparative Example 2 (No Modified Interlayer) - Comparative Example 2 (CE 2) is a solid-state lithium metal symmetric cell without a modified interlayer. The symmetric cell is assembled as follows. First, a nanogold layer is sputtered on the surface of LLZT-2LWO for 5 minutes. Then the LLZT-2LWO is placed in a glove box filled with argon. A lithium sheet is placed in the center of the LLZT-2LWO surface and heated to 250-300°C on a hot plate. The molten lithium metal is evenly spread on the surface of LLZT-2LWO. The same operation is repeated on the other side to obtain a symmetric cell. In addition, a solid-state lithium metal full cell without a modified interlayer, lithium metal is obtained by melting lithium using the above method, and secondly, a small amount of electrolyte (1:3 molar LiTFSI and cyclopentane sulfone (TMS) solution) is dripped on the cathode side to obtain good interface contact. The components are then assembled in a CR2025 button cell for testing.
[0201] Solid-state lithium metal symmetric cells without modified interlayers showed only 0.9 mA / cm at 25 °C 2 In addition, a solid-state lithium metal full battery without a modified interlayer has a critical current density of 21 mg / cm at the cathode. 2 The cycling performance test was carried out under NCM load. The relationship between the battery voltage, discharge capacity and cycle number is as follows: Fig.28 As shown, the battery is overcharged in the second cycle, indicating the growth of lithium dendrites.
[0202] Thermal curing VEC modified interlayer
[0203] Table 1 gives the properties of the symmetric cells assembled for Examples 1-2 and 5-7 and Comparative Example 2. Table 2 shows the properties of the full cells assembled for Examples 1*, 6* and 7* and Comparative Example 2. Examples 1*, 6* and 7* correspond to Examples 1, 6 and 7, respectively, except that an NCM cathode and an electrolyte solution between the NCM cathode and the solid electrolyte are used. As shown in this section and Tables 1-2, "vinyl" refers to a modified interlayer prepared by thermally curing a modified reaction mixture including VEC with an electrospun polymer, while "methacrylate" refers to a modified interlayer prepared by UV curing a modified reaction mixture including PEGMEMA and an electrospun polymer. As shown in this section and Tables 1-2, "SiC" refers to a solid electrolyte polished using 1200 mesh SiC as described herein, and "etched" refers to a solid electrolyte etched with a 2 molar HCl solution for 1 minute ("etched").
[0204] Example 6 (1 wt% DCA, polished solid electrolyte - Example 6 includes a SiC polished solid electrolyte prepared in the same manner as Example 1, and the solution prepared during the solution preparation step includes 1.0 wt% of D(+)-10-camphorsulfonic acid (DCA) as in Embodiment 1. However, the modified reaction mixture of Example 6 includes vinyl ethylene carbonate (VEC) instead of PEGMEMA in Example 1 as a crosslinkable monomer or prepolymer, and the modified mixture in Example 6 includes 0.5 wt% of 2,2'-azobis(2-methylpropionitrile) (AIBN) based on the weight of VEC as a thermal initiator instead of the HMPP photoinitiator in Example 1. 20 μL of the modified reaction mixture was added dropwise to the electrospinning polymer. After waiting for 30 minutes, the electrospinning polymer including the absorbed modified reaction mixture was placed between the SiC polished solid electrolyte and the lithium sheet. The modified intermediate layer was formed by curing the modified reaction mixture by heating the lithium sheet, the SiC polished solid electrolyte, and the electrospinning polymer including the absorbed modified reaction mixture at 70°C for 2 hours.
[0205] The solid-state lithium metal symmetric cell assembled from the modified interlayer of Example 6 (1 wt% DCA, vinyl cross-linkable monomer) and the solid electrolyte (SiC polishing) exhibited a current of 4.0 mA / cm at 25 °C. 2 Thus, Example 6 (thermally cured vinyl crosslinkable monomer) achieves the same CCD as Example 1 (UV cured methacrylate crosslinkable monomer), indicating that both crosslinking monomers can perform equally well when used in combination with SiC polished solid electrolytes. In addition, Example 6 has a CCD of 388 Ωcm 2 The interface impedance.
[0206] Example 7 (1 wt% DCA, etched solid electrolyte) - Example 7 is the same as Example 6 (including the same modified intermediate layer), except that in Example 7, an etched solid electrolyte (porous surface) is used instead of SiC polishing the solid electrolyte (smooth surface).
[0207] The solid-state lithium metal symmetric cell assembled from the modified interlayer of Example 7 (1 wt% DCA, vinyl cross-linking monomer) and the solid electrolyte (etched) exhibited a current of 5.1 mA / cm at 25 °C. 2 Compared with Example 6 (SiC polished solid electrolyte, thermally cured modified interlayer), the combination of thermally cured modified interlayer and the porous surface produced by etching the solid electrolyte increased the CCD from 4.0 mA / cm 2 Increased to 5.1 mA / cm 2. It is believed that the increase in CCD is the result of a portion of the modified interlayer being located in the pores of the porous surface of the solid electrolyte, which increases the contact area between the modified interlayer and the solid electrolyte (compared to a solid electrolyte with a smooth surface). Unlike the UV-cured modified interlayer (Example 5), a portion of the thermally cured modified interlayer can be located in the pores of the etched solid electrolyte because the precursors (electrospinning polymer and / or absorbed modification reaction mixture) are in contact with the pores and / or can flow into the pores prior to curing. In fact, Example 7 (thermally cured and etched solid electrolyte, 5.1 mA / cm 2 ) has a higher conductivity than Example 5 (UV-cured electrolyte and etched solid electrolyte, 2.8 mA / cm 2 ) is much higher than the CCD of Example 7. In addition, Example 7 has 202Ωcm 2 Among the examples given in Table 1, Example 7 has the lowest interfacial impedance, which is consistent with the explanation that a portion of the heat-cured modified intermediate layer is located in the pores of the porous surface of the solid electrolyte.
[0208] Table 1 Properties of Examples 1-2 and 5-7 and Comparative Example 2
[0209] Table 2 gives the characteristics of the full cells assembled from Examples 1*, 6* and 7* and Comparative Example 2. Examples 1*, 6* and 7* correspond to Examples 1, 6 and 7, respectively, except that an NCM cathode and an electrolyte between the NCM cathode and the solid electrolyte are used. Similarly, Comparative Example 2* corresponds to Comparative Example 2, except that an NCM cathode and an electrolyte between the NCM cathode and the solid electrolyte are used. As shown in Table 2, Examples 1*, 6* and 7* include a loading of 21 mg / cm 2 NCM cathode. Comparative Example 2* also has a 2 The test was conducted at a cathode loading of 21 mg / cm 2 The cathode was short-circuited in the second cycle of loading. As described above, Example 1* at 0.45 mA / cm 2 The capacity retention rate is 88% after 50 cycles at 25 °C.
[0210] Fig.32 Shown at 0.45mA / cm 2 The specific capacity (mAh / cm2) of Example 6* cycled at 25°C 2 ) and Coulombic efficiency (%). The solid circles correspond to the specific capacity measurements, while the hollow circles correspond to the Coulombic efficiency measurements. Fig.32As shown, Example 6* exhibited a capacity retention of 86% after 67 cycles. However, Example 6* short-circuited (SC) during 68 cycles. Fig.33 Curves are shown for cycle numbers 1, 25, 50, and 68. The curves for cycles 1, 25, and 50 cycled normally. However, as shown in the cycle curve for cycle 68 (charging), the battery was overcharged and shorted.
[0211] Fig.30 Shown at 0.45mA / cm 2 The specific capacity (mAh / cm2) of Example 7* cycled at 25°C 2 ) and Coulombic efficiency (%). The solid circles correspond to the specific capacity measurements, while the hollow circles correspond to the Coulombic efficiency measurements. Fig.30 As shown, Example 7* exhibited a capacity retention of 79% after 87 cycles and a capacity retention of 71% after 100 cycles. Fig.31 Cycle curves for cycle numbers 1, 25, 50, 75 and 100 are shown.
[0212] Table 2 Properties of Examples 1*, 6* and 7 and Comparative Example 2*
[0213] It is obvious to those skilled in the art that various modifications and changes can be made to the embodiments described herein without departing from the scope and range of the subject matter of the claims. Therefore, this specification is intended to cover modifications and changes of the various embodiments described herein, as long as such modifications and changes are within the scope of the attached claims and their equivalents.
Claims
1. A solid-state lithium-containing battery, characterized in that: The solid-state lithium-containing battery comprises: electrode; solid electrolyte; and A modified intermediate layer, the modified intermediate layer is located between the electrode and the solid electrolyte and is in direct contact therewith, the modified intermediate layer comprising: A three-dimensional polymer framework comprising (i) electrospun polymer nanofibers having a diameter in the range of 10 nm to 50 nm, (ii) a framework additive contained in the electrospun polymer nanofibers, the framework additive comprising a sulfonic acid-containing compound, and (iii) pores between the electrospun polymer nanofibers; a cross-linked polymer in the pores of the three-dimensional polymer framework; Cross-linking solvents in the pores of the three-dimensional polymer framework; and Lithium salts in the pores of three-dimensional polymer frameworks.
2. The solid-state lithium-containing battery according to claim 1, characterized in that: The electrospun polymer nanofibers include one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyvinylidene fluoride, polyurethane, polyacrylonitrile, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyacrylic acid, carboxymethyl cellulose, polyethylene oxide, poly(acrylonitrile-co-butadiene-co-styrene) and polyimide.
3. The solid-state lithium-containing battery according to claim 2, characterized in that: The electrospun polymer nanofibers include poly(vinylidene fluoride-co-hexafluoropropylene).
4. The solid-state lithium-containing battery according to claim 1, characterized in that: The sulfonic acid-containing compound includes one or more of D(+)-10-camphorsulfonic acid, DL-10-camphorsulfonic acid, L(-)-camphorsulfonic acid, benzenesulfonic acid, o-cresol-4-sulfonic acid and 2-naphthalenesulfonic acid.
5. The solid-state lithium-containing battery according to claim 4, characterized in that: The sulfonic acid-containing compound includes D(+)-10-camphorsulfonic acid.
6. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The three-dimensional polymer framework is substantially free of nodules of electrospun polymer nanofibers.
7. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The cross-linked polymer includes a cross-linked polymer network including units of one or more of ether-containing acrylates, ether-containing methacrylates, alkyl carbonates, or combinations thereof.
8. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The crosslinked polymer network of the crosslinked polymer includes a fluoroether additive.
9. The solid-state lithium-containing battery according to claim 8, characterized in that The fluoroether additive includes one or more of polyperfluoromethyl isopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), and fluorobenzene (FB).
10. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The cross-linking solvent includes one or more of fluoroethylene carbonate (FEC), vinyl carbonate (VC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene sulfinate (FES), difluoroethylene carbonate (DFEC) and trifluoroethyl methyl carbonate (FEMC).
11. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The lithium salt includes lithium bistrifluoromethanesulfonyl imide (LiTFSI).
12. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The modified intermediate layer has a compressed thickness when compressed between the electrode and the solid electrolyte, and has an uncompressed thickness when not compressed between the electrode and the solid electrolyte, and a ratio of the uncompressed thickness to the compressed thickness is 2 to 10.
13. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: When the modified intermediate layer is compressed, the compressed thickness between the electrode and the solid electrolyte is in the range of 2 μm to 20 μm.
14. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The ionic conductivity of the modified interlayer at 25°C is 4.5×10 -4 S / cm to 7.5×10 -4 S / cm range.
15. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The electrode is a lithium-containing anode, and the modified intermediate layer is located between the lithium-containing anode and the solid electrolyte.
16. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The electrode includes lithium metal.
17. The solid-state lithium-containing battery according to claim 1, characterized in that: The solid-state lithium-containing battery further comprises: A second electrode comprises a lithium metal electrode, wherein a solid electrolyte is located between the electrode and the second electrode, wherein the solid-state lithium-containing battery is a solid-state lithium metal symmetric battery.
18. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid electrolyte includes lithium garnet ceramic.
19. The solid-state lithium-containing battery according to claim 18, characterized in that The main phase of the lithium garnet ceramic includes at least one of the following: (i)Li 7-3a LqCy a O 12 , characterized in that Q = Al, Ga or Fe, and 0<a<0.33; (ii)Li7La 3-b ZlUT b O 12 , characterized in that M = Bi or Y, and 0<b<1; (iii)Li 7-c LqCy 2-c N c O 12 , characterized in that N=In, Si, Ge, Sn, V, W, Te, Nb or Ta, and 0<c<1, or a combination thereof.
20. The solid-state lithium-containing battery according to claim 18, characterized in that The main phase of the lithium garnet ceramic includes Li7La3Zr2O 12 .
21. The solid-state lithium-containing battery according to claim 18, characterized in that The lithium garnet ceramic has a main phase of lithium garnet ceramic doped with one or more dopants.
22. The solid-state lithium-containing battery according to claim 18, characterized in that The solid electrolyte is a composite material composed of two or more ceramic materials.
23. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid-state lithium-containing battery further comprises: A cathode comprising one or more of the following: lithium cobalt oxide (LiCoO2); lithium nickel oxide (LiNiO2); 1+x Mn 2-x Lithium manganate represented by O4, wherein x is 0 to 0.33; LiNi 1-y M y Ni-type lithium nickel oxide represented by O2, wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3; LiNi z Co m Mn 1-z-m A lithium nickel cobalt manganese material represented by O2, wherein x is 0 to 1, y is 0 to 1, and z+m<1; and combinations thereof; and The electrolyte, located between the cathode and the solid electrolyte; wherein the electrode is a cathode; Wherein, the solid-state lithium-containing battery is a solid-state lithium-containing full battery.
24. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid-state lithium-containing battery has a current of ≥3.5 mA / cm at 25°C. 2 The critical current density.
25. A solid-state lithium-containing battery according to claim 24, characterized in that The solid-state lithium-containing battery has a current of ≥4.5 mA / cm at 25°C. 2 The critical current density.
26. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid-state lithium-containing battery has a coulombic efficiency of ≥90% in at least 50 charge and discharge cycles at 25° C. and 0.5C.
27. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid-state lithium-containing battery has a coulombic efficiency of ≥90% in at least 200 charge and discharge cycles at 25° C. and 0.5C.
28. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: After the solid-state lithium-containing battery is charged and discharged for 50 cycles at 0.5C and 25°C, the capacity retention rate is ≥80%.
29. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: After 100 cycles of charging and discharging at 0.5C and 25°C, the capacity retention rate of the solid-state lithium-containing battery is ≥90%.
30. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid-state lithium-containing battery has an interface resistance of ≤400Ωcm at 25°C 2 .
31. A solid-state lithium-containing battery according to claim 30, characterized in that The solid-state lithium-containing battery has an interface resistance of ≤250Ωcm at 25°C 2 .
32. The solid-state lithium-containing battery according to any one of claims 1 to 5, characterized in that: The solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte.
33. A method for manufacturing a solid-state lithium-containing battery, characterized in that: include: electrospinning a solution comprising a polymer and a framework additive to obtain a three-dimensional (3D) polymer framework, wherein the three-dimensional polymer framework comprises (i) electrospun polymer nanofibers and (ii) pores between electrospun polymer nanofibers, wherein the electrospun polymer nanofibers comprise the polymer and the framework additive integrated into the electrospun polymer nanofibers; and contacting the three-dimensional polymer framework with a monomer reaction mixture comprising (i) a cross-linkable monomer or prepolymer, (ii) a cross-linking solvent, and (iii) a lithium salt; reacting a crosslinkable monomer or prepolymer in the monomer reaction mixture to form a modified interlayer, the modified interlayer comprising (i) the three-dimensional polymer framework, (ii) a crosslinking polymer within the pores of the three-dimensional polymer framework, (iii) a crosslinking solvent within the pores of the three-dimensional polymer framework, and (iv) a lithium salt within the pores of the three-dimensional polymer framework, The framework additive comprises a sulfonic acid-containing compound.
34. The method according to claim 33, characterized in that The polymer includes one or more of poly(vinylidene fluoride-co-hexafluoropropylene), polyvinylidene fluoride, polyurethane, polyacrylonitrile, polyvinyl alcohol, polyethylene glycol, polymethyl methacrylate, polyacrylic acid, carboxymethyl cellulose, polyethylene oxide, poly(acrylonitrile-co-butadiene-co-styrene) and polyimide.
35. The method according to claim 33, characterized in that The weight percentage of the framework additive is in the range of 0.10 wt % to 3.0 wt %.
36. The method according to claim 33, characterized in that The sulfonic acid-containing compound includes one or more of D(+)-10-camphorsulfonic acid, DL-10-camphorsulfonic acid, L(-)-camphorsulfonic acid, benzenesulfonic acid, o-cresol-4-sulfonic acid and 2-naphthalenesulfonic acid.
37. The method according to claim 36, characterized in that The sulfonic acid-containing compound comprises D(+)-10-camphorsulfonic acid.
38. The method according to claim 36, characterized in that The three-dimensional polymer framework exhibits an absorption capacity of greater than or equal to 800% of the monomer reaction mixture.
39. The method according to any one of claims 33 to 38, characterized in that The crosslinkable monomer or prepolymer comprises one or more alcohol-containing acrylates, alcohol-containing methacrylates, vinyl carbonate or a combination thereof.
40. The method according to any one of claims 33 to 38, characterized in that The crosslinkable monomers or prepolymers include diethylene glycol diacrylate (DEGDA), diethylene glycol dimethacrylate (DEGDMA), triethylene glycol diacrylate (TEGDA), triethylene glycol dimethacrylate (TEGDMA), tetraethylene glycol diacrylate (TTEGDA), glycidyl methacrylate, polyethylene glycol diacrylate (PEGDA), polyethylene glycol dimethacrylate (PEGDMA), polypropylene glycol diacrylate (PPGDA), dipropylene glycol diacrylate (DPGDA), tripropylene glycol diacrylate (TPGDA), dipropylene glycol diacrylate (DDA), dipropylene glycol dimethacrylate (DDMA), ethoxylated trimethylolpropane triacrylate (ETPTA), acrylate functionalized ethylene oxide, butanediol dimethacrylate, ethoxylated One or more of neopentyl glycol diacrylate (NPEOGDA), propoxylated neopentyl glycol diacrylate (NPPOGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane triacrylate (TMPTMA), pentaerythritol triacrylate (PETA), ethoxylated propoxylated trimethylolpropane triacrylate (TMPEOTA) / (TMPPOTA), propoxylated glycerol triacrylate, tris(2-hydroxyethyl)isocyanurate (THEICTA), pentaerythritol tetraacrylate (PETTA), pentaerythritol pentaacrylate (DPEPA), dimethylenepropane tetraacrylate (DTMPTTA), diglycidyl esters, diallyl esters, acrylamide, divinylbenzene and poly(ethylene glycol methyl ether methacrylate) (PEGMEMA).
41. The method according to any one of claims 33 to 38, characterized in that The cross-linkable monomer or prepolymer includes vinyl ethylene carbonate.
42. The method according to any one of claims 33 to 38, characterized in that The cross-linking solvent includes one or more of fluoroethylene carbonate (FEC), vinyl carbonate (VC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and fluoroethylene sulfinate (FES).
43. The method according to any one of claims 33 to 38, characterized in that The lithium salt includes lithium bistrifluoromethanesulfonyl imide (LiTFSI).
44. The method according to any one of claims 33 to 38, characterized in that The monomer reaction mixture further comprises a fluoroether additive.
45. The method according to any one of claims 33 to 38, characterized in that The fluoroether additive includes one or more of polyperfluoromethyl isopropyl ether (PFPE), fluorinated ether of bis(2,2-difluoroethyl) ether (BDE), 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether (THE), 1,3,5-trifluorobenzene (3FB), and fluorobenzene (FB).
46. The method according to any one of claims 33 to 38, characterized in that The monomer reaction mixture further comprises a photoinitiator, and the reacting comprises irradiating the crosslinkable monomers or prepolymers in the monomer reaction mixture with ultraviolet light.
47. The method according to any one of claims 33 to 38, characterized in that The method further comprises: The modified intermediate layer is disposed between the lithium-containing electrode and the solid electrolyte.
48. The method according to any one of claims 33 to 38, characterized in that The monomer reaction mixture further comprises a thermal initiator, and the reacting comprises heating the monomer reaction mixture.
49. The method according to claim 48, characterized in that The method further includes positioning the three-dimensional polymer framework and the monomer reaction mixture between a lithium-containing electrode and a solid electrolyte after the contacting and before the reacting.
50. The method according to claim 49, characterized in that The solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte.
51. A method according to claim 47, 49 or 50, characterised in that The solid electrolyte includes lithium garnet ceramic.
52. The method according to any one of claims 33 to 38, characterized in that The modified intermediate layer has a compressed thickness when compressed between the electrode and the solid electrolyte, has an uncompressed thickness when uncompressed between the electrode and the solid electrolyte, and a ratio of the uncompressed thickness to the compressed thickness is 2 to 10.
53. The method according to any one of claims 33 to 38, characterized in that The solid-state lithium-containing battery has a current of ≥3.5 mA / cm at 25°C. 2 The critical current density.
54. The method according to any one of claims 33 to 38, characterized in that After the solid-state lithium-containing battery is charged and discharged for 50 cycles at 0.5C and 25°C, the capacity retention rate is ≥80%.
55. The method according to any one of claims 33 to 38, characterized in that After 100 cycles of charging and discharging at 0.5C and 25°C, the capacity retention rate of the solid-state lithium-containing battery is ≥90%.
56. The method according to any one of claims 33 to 38, characterized in that The interface resistance of the solid-state lithium-containing battery at 25°C is ≤400Ωcm 2 .
57. The method according to claim 56, characterized in that The interface resistance of the solid-state lithium-containing battery at 25°C is ≤250Ωcm 2 .
58. The method according to any one of claims 33 to 38, characterized in that The solid electrolyte includes pores, and at least a portion of the modified intermediate layer is located within the pores of the solid electrolyte.
Citation Information
Cited By
Three-dimensional polymer modified intermediate layer for lithium ion solid-state battery and preparation method of three-dimensional polymer modified intermediate layer
CN121618063A
A three-dimensional polymer-modified interlayer for lithium-ion solid-state batteries and a method for preparing the same
CN121618063B